Dynamics and interactions of AAC3 in DPC are not functionally relevant - Kurauskas, Vilius; Hessel, Audrey; Dehez, François; Chipot, Christophe; Bersch, Beate; Schanda, Paul (Nature Structural & Molecular Biology)
Keywords: Molecular Biology; Structural Biology

Diffusiophoretic design of self-spinning microgears from colloidal microswimmers - Aubret, Antoine; Palacci, Jérémie A (Soft Matter)
The development of strategies to assemble microscopic machines from dissipative building blocks are essential on the route to novel active materials. We recently demonstrated the hierarchical self-assembly of phoretic microswimmers into self-spinning microgears and their synchronization by diffusiophoretic interactions [Aubret et al., Nat. Phys., 2018]. In this paper, we adopt a pedagogical approach and expose our strategy to control self-assembly and build machines using phoretic phenomena. We notably introduce Highly Inclined Laminated Optical sheets microscopy (HILO) to image and characterize anisotropic and dynamic diffusiophoretic interactions, which cannot be performed by conventional fluorescence microscopy. The dynamics of a (haematite) photocatalytic material immersed in (hydrogen peroxide) fuel under various illumination patterns is first described and quantitatively rationalized by a model of diffusiophoresis, the migration of a colloidal particle in a concentration gradient. It is further exploited to design phototactic microswimmers that direct towards the high intensity of light, as a result of the reorientation of the haematite in a light gradient. We finally show the assembly of self-spinning microgears from colloidal microswimmers and carefully characterize the interactions using HILO techniques. The results are compared with analytical and numerical predictions and agree quantitatively, stressing the important role played by concentration gradients induced by chemical activity to control and design interactions. Because the approach described hereby is generic, this works paves the way for the rational design of machines by controlling phoretic phenomena.
Keywords: General Chemistry; Condensed Matter Physics

Antiferromagnet‐based spintronic functionality by controlling isospin domains in a layered perovskite iridate - Lee, Nara; Ko, Eunjung; Choi, Hwan Young; Hong, Yun Jeong; Nauman, Muhammad; Kang, Woun; Choi, Hyoung Joon; Choi, Young Jai; Jo, Younjung (Advanced Materials)
The novel electronic state of the canted antiferromagnetic (AFM) insulator, strontium iridate (Sr2IrO4) has been well described by the spin-orbit-entangled isospin Jeff = 1/2, but the role of isospin in transport phenomena remains poorly understood. In this study, antiferromagnet-based spintronic functionality is demonstrated by combining unique characteristics of the isospin state in Sr2IrO4. Based on magnetic and transport measurements, large and highly anisotropic magnetoresistance (AMR) is obtained by manipulating the antiferromagnetic isospin domains. First-principles calculations suggest that electrons whose isospin directions are strongly coupled to in-plane net magnetic moment encounter the isospin mismatch when moving across antiferromagnetic domain boundaries, which generates a high resistance state. By rotating a magnetic field that aligns in-plane net moments and removes domain boundaries, the macroscopically-ordered isospins govern dynamic transport through the system, which leads to the extremely angle-sensitive AMR. As with this work that establishes a link between isospins and magnetotransport in strongly spin-orbit-coupled AFM Sr2IrO4, the peculiar AMR effect provides a beneficial foundation for fundamental and applied research on AFM spintronics.
Keywords: Mechanical Engineering; General Materials Science; Mechanics of Materials

Pressure-induced metal–insulator transitions in chalcogenide NiS2-Se - Hussain, Tayyaba; Oh, Myeong-jun; Nauman, Muhammad; Jo, Younjung; Han, Garam; Kim, Changyoung; Kang, Woun (Physica B: Condensed Matter)
We report the temperature-dependent resistivity ρ(T) of chalcogenide NiS2-xSex (x = 0.1) using hydrostatic pressure as a control parameter in the temperature range of 4–300 K. The insulating behavior of ρ(T) survives at low temperatures in the pressure regime below 7.5 kbar, whereas a clear insulator-to-metallic transition is observed above 7.5 kbar. Two types of magnetic transitions, from the paramagnetic (PM) to the antiferromagnetic (AFM) state and from the AFM state to the weak ferromagnetic (WF) state, were evaluated and confirmed by magnetization measurement. According to the temperature–pressure phase diagram, the WF phase survives up to 7.5 kbar, and the transition temperature of the WF transition decreases as the pressure increases, whereas the metal–insulator transition temperature increases up to 9.4 kbar. We analyzed the metallic behavior and proposed Fermi-liquid behavior of NiS1.9Se0.1.

Scaling precipitation extremes with temperature in the Mediterranean: Past climate assessment and projection in anthropogenic scenarios - Drobinski, Philippe; Silva, Nicolas Da; Panthou, Gérémy; Bastin, Sophie; Muller, Caroline J; Ahrens, Bodo; Borga, Marco; Conte, Dario; Fosser, Giorgia; Giorgi, Filippo; Güttler, Ivan; Kotroni, Vassiliki; et al. (Climate Dynamics)
In this study we investigate the scaling of precipitation extremes with temperature in the Mediterranean region by assessing against observations the present day and future regional climate simulations performed in the frame of the HyMeX and MED-CORDEX programs. Over the 1979–2008 period, despite differences in quantitative precipitation simulation across the various models, the change in precipitation extremes with respect to temperature is robust and consistent. The spatial variability of the temperature–precipitation extremes relationship displays a hook shape across the Mediterranean, with negative slope at high temperatures and a slope following Clausius–Clapeyron (CC)-scaling at low temperatures. The temperature at which the slope of the temperature–precipitation extreme relation sharply changes (or temperature break), ranges from about 20 °C in the western Mediterranean to <10 °C in Greece. In addition, this slope is always negative in the arid regions of the Mediterranean. The scaling of the simulated precipitation extremes is insensitive to ocean–atmosphere coupling, while it depends very weakly on the resolution at high temperatures for short precipitation accumulation times. In future climate scenario simulations covering the 2070–2100 period, the temperature break shifts to higher temperatures by a value which is on average the mean regional temperature change due to global warming. The slope of the simulated future temperature–precipitation extremes relationship is close to CC-scaling at temperatures below the temperature break, while at high temperatures, the negative slope is close, but somewhat flatter or steeper, than in the current climate depending on the model. Overall, models predict more intense precipitation extremes in the future. Adjusting the temperature–precipitation extremes relationship in the present climate using the CC law and the temperature shift in the future allows the recovery of the temperature–precipitation extremes relationship in the future climate. This implies negligible regional changes of relative humidity in the future despite the large warming and drying over the Mediterranean. This suggests that the Mediterranean Sea is the primary source of moisture which counteracts the drying and warming impacts on relative humidity in parts of the Mediterranean region.
Keywords: Atmospheric Science

Internal tide dissipation at topography: Triadic resonant instability equatorward and evanescent waves poleward of the critical latitude - Richet, O.; Chomaz, J.-M.; Muller, Caroline J (Journal of Geophysical Research: Oceans)
Several studies have shown the existence of a critical latitude where the dissipation of internal tides is strongly enhanced. Internal tides are internal waves generated by barotropic tidal currents impinging rough topography at the seafloor. Their dissipation and concomitant diapycnal mixing are believed to be important for water masses and the large‐scale ocean circulation. The purpose of this study is to clarify the physical processes at the origin of this strong latitudinal dependence of tidal energy dissipation. We find that different mechanisms are involved equatorward and poleward of the critical latitude. Triadic resonant instabilities are responsible for the dissipation of internal tides equatorward of the critical latitude. In particular, a dominant triad involving the primary internal tide and near‐inertial waves is key. At the critical latitude, the peak of energy dissipation is explained by both increased instability growth rates, and smaller scales of secondary waves thus more prone to break and dissipate their energy. Surprisingly, poleward of the critical latitude, the generation of evanescent waves appears to be crucial. Triadic instabilities have been widely studied, but the transfer of energy to evanescent waves has received comparatively little attention. Our work suggests that the nonlinear transfer of energy from the internal tide to evanescent waves (corresponding to the 2f‐pump mechanism described by Young et al., 2008, https://doi.org/10.1017/S0022112008001742) is an efficient mechanism to dissipate internal tide energy near and poleward of the critical latitude. The theoretical results are confirmed in idealized high‐resolution numerical simulations of a barotropic M2 tide impinging sinusoidal topography in a linearly stratified fluid.

Acceleration of tropical cyclogenesis by self-aggregation feedbacks - Muller, Caroline J; Romps, David M. (Proceedings of the National Academy of Sciences)
Idealized simulations of tropical moist convection have revealed that clouds can spontaneously clump together in a process called self-aggregation. This results in a state where a moist cloudy region with intense deep convection is surrounded by extremely dry subsiding air devoid of deep convection. Because of the idealized settings of the simulations where it was discovered, the relevance of self-aggregation to the real world is still debated. Here, we show that self-aggregation feedbacks play a leading-order role in the spontaneous genesis of tropical cyclones in cloud-resolving simulations. Those feedbacks accelerate the cyclogenesis process by a factor of 2, and the feedbacks contributing to the cyclone formation show qualitative and quantitative agreement with the self-aggregation process. Once the cyclone is formed, wind-induced surface heat exchange (WISHE) effects dominate, although we find that self-aggregation feedbacks have a small but nonnegligible contribution to the maintenance of the mature cyclone. Our results suggest that self-aggregation, and the framework developed for its study, can help shed more light into the physical processes leading to cyclogenesis and cyclone intensification. In particular, our results point out the importance of the longwave radiative cooling outside the cyclone.
Keywords: Multidisciplinary

FACT complex is required for DNA demethylation at heterochromatin during reproduction in Arabidopsis - Frost, Jennifer M.; Kim, M. Yvonne; Park, Guen Tae; Hsieh, Ping-Hung; Nakamura, Miyuki; Lin, Samuel J. H.; Yoo, Hyunjin; Choi, Jaemyung; Ikeda, Yoko; Kinoshita, Tetsu; Choi, Yeonhee; Zilberman, Daniel; et al. (Proceedings of the National Academy of Sciences)
The DEMETER (DME) DNA glycosylase catalyzes genome-wide DNA demethylation and is required for endosperm genomic imprinting and embryo viability. Targets of DME-mediated DNA demethylation reside in small, euchromatic, AT-rich transposons and at the boundaries of large transposons, but how DME interacts with these diverse chromatin states is unknown. The STRUCTURE SPECIFIC RECOGNITION PROTEIN 1 (SSRP1) subunit of the chromatin remodeler FACT (facilitates chromatin transactions), was previously shown to be involved in the DME-dependent regulation of genomic imprinting in Arabidopsis endosperm. Therefore, to investigate the interaction between DME and chromatin, we focused on the activity of the two FACT subunits, SSRP1 and SUPPRESSOR of TY16 (SPT16), during reproduction in Arabidopsis. We found that FACT colocalizes with nuclear DME in vivo, and that DME has two classes of target sites, the first being euchromatic and accessible to DME, but the second, representing over half of DME targets, requiring the action of FACT for DME-mediated DNA demethylation genome-wide. Our results show that the FACT-dependent DME targets are GC-rich heterochromatin domains with high nucleosome occupancy enriched with H3K9me2 and H3K27me1. Further, we demonstrate that heterochromatin-associated linker histone H1 specifically mediates the requirement for FACT at a subset of DME-target loci. Overall, our results demonstrate that FACT is required for DME targeting by facilitating its access to heterochromatin.
Keywords: Multidisciplinary

Collisional charging of individual submillimeter particles: Using ultrasonic levitation to initiate and track charge transfer - Lee, Victor; James, Nicole; Waitukaitis, Scott R; Jaeger, Heinrich (Physical Review Materials)
Electrostatic charging of insulating fine particles can be responsible for numerous phenomena ranging from lightning in volcanic plumes to dust explosions. However, even basic aspects of how fine particles become charged are still unclear. Studying particle charging is challenging because it usually involves the complexities associated with many-particle collisions. To address these issues, we introduce a method based on acoustic levitation, which makes it possible to initiate sequences of repeated collisions of a single submillimeter particle with a flat plate, and to precisely measure the particle charge in situ after each collision. We show that collisional charge transfer between insulators is dependent on the hydrophobicity of the contacting surfaces. We use glass, which we modify by attaching nonpolar molecules to the particle, the plate, or both. We find that hydrophilic surfaces develop significant positive charges after contacting hydrophobic surfaces. Moreover, we demonstrate that charging between a hydrophilic and a hydrophobic surface is suppressed in an acidic environment and enhanced in a basic one. Application of an electric field during each collision is found to modify the charge transfer, again depending on surface hydrophobicity. We discuss these results within the context of contact charging due to ion transfer, and we show that they lend strong support to OH− ions as the charge carriers.

The random k‐matching‐free process - Krivelevich, Michael; Kwan, Matthew Alan; Loh, Po‐Shen; Sudakov, Benny (Random Structures and Algorithms)
Let P be a graph property which is preserved by removal of edges, and consider the random graph process that starts with the empty n-vertex graph and then adds edges one-by-one, each chosen uniformly at random subject to the constraint that P is not violated. These types of random processes have been the subject of extensive research over the last 20 years, having striking applications in extremal combinatorics, and leading to the discovery of important probabilistic tools. In this paper we consider the k-matching-free process, where P is the property of not containing a matching of size k. We are able to analyse the behaviour of this process for a wide range of values of k; in particular we prove that if k=o(n) or if n−2k=o(n−−√/logn) then this process is likely to terminate in a k-matching-free graph with the maximum possible number of edges, as characterised by Erdős and Gallai. We also show that these bounds on k are essentially best possible, and we make a first step towards understanding the behaviour of the process in the intermediate regime.

Counting Hamilton cycles in sparse random directed graphs - Ferber, Asaf; Kwan, Matthew Alan; Sudakov, Benny (Random Structures and Algorithms)
Let D(n,p) be the random directed graph on n vertices where each of the n(n-1) possible arcs is present independently with probability p. A celebrated result of Frieze shows that if p≥(logn+ω(1))/n then D(n,p) typically has a directed Hamilton cycle, and this is best possible. In this paper, we obtain a strengthening of this result, showing that under the same condition, the number of directed Hamilton cycles in D(n,p) is typically n!(p(1+o(1)))n. We also prove a hitting-time version of this statement, showing that in the random directed graph process, as soon as every vertex has in-/out-degrees at least 1, there are typically n!(logn/n(1+o(1)))n directed Hamilton cycles.

Intercalates and discrepancy in random Latin squares - Kwan, Matthew Alan; Sudakov, Benny (Random Structures and Algorithms)
An intercalate in a Latin square is a 2×2 Latin subsquare. Let N be the number of intercalates in a uniformly random n×n Latin square. We prove that asymptotically almost surely N≥(1−o(1))n2/4, and that EN≤(1+o(1))n2/2 (therefore asymptotically almost surely N≤fn2 for any f→∞). This significantly improves the previous best lower and upper bounds. We also give an upper tail bound for the number of intercalates in two fixed rows of a random Latin square. In addition, we discuss a problem of Linial and Luria on low-discrepancy Latin squares.

Non-trivially intersecting multi-part families - Kwan, Matthew Alan; Sudakov, Benny; Vieira, Pedro (Journal of Combinatorial Theory Series A)
We say a family of sets is intersecting if any two of its sets intersect, and we say it is trivially intersecting if there is an element which appears in every set of the family. In this paper we study the maximum size of a non-trivially intersecting family in a natural “multi-part” setting. Here the ground set is divided into parts, and one considers families of sets whose intersection with each part is of a prescribed size. Our work is motivated by classical results in the single-part setting due to Erdős, Ko and Rado, and Hilton and Milner, and by a theorem of Frankl concerning intersecting families in this multi-part setting. In the case where the part sizes are sufficiently large we determine the maximum size of a non-trivially intersecting multi-part family, disproving a conjecture of Alon and Katona.

Hydrogen diffusion and trapping in α-iron: The role of quantum and anharmonic fluctuations - Cheng, Bingqing; Paxton, Anthony T.; Ceriotti, Michele (Physical Review Letters)
We investigate the thermodynamics and kinetics of a hydrogen interstitial in magnetic α-iron, taking account of the quantum fluctuations of the proton as well as the anharmonicities of lattice vibrations and hydrogen hopping. We show that the diffusivity of hydrogen in the lattice of bcc iron deviates strongly from an Arrhenius behavior at and below room temperature. We compare a quantum transition state theory to explicit ring polymer molecular dynamics in the calculation of diffusivity. We then address the trapping of hydrogen by a vacancy as a prototype lattice defect. By a sequence of steps in a thought experiment, each involving a thermodynamic integration, we are able to separate out the binding free energy of a proton to a defect into harmonic and anharmonic, and classical and quantum contributions. We find that about 30% of a typical binding free energy of hydrogen to a lattice defect in iron is accounted for by finite temperature effects, and about half of these arise from quantum proton fluctuations. This has huge implications for the comparison between thermal desorption and permeation experiments and standard electronic structure theory. The implications are even greater for the interpretation of muon spin resonance experiments.

Communication: Computing the Tolman length for solid-liquid interfaces - Cheng, Bingqing; Ceriotti, Michele (The Journal of Chemical Physics)
The curvature dependence of interfacial free energy, which is crucial in quantitatively predicting nucleation kinetics and the stability of bubbles and droplets, is quantified by the Tolman length δ. For solid-liquid interfaces, however, δ has never been computed directly due to various theoretical and practical challenges. Here we perform a direct evaluation of the Tolman length from atomistic simulations of a solid-liquid planar interface in out-of-equilibrium conditions, by first computing the surface tension from the amplitude of thermal capillary fluctuations of a localized version of the Gibbs dividing surface and by then calculating how much the surface energy changes when it is defined relative to the equimolar dividing surface. We computed δ for a model potential, and found a good agreement with the values indirectly inferred from nucleation simulations. The agreement not only validates our approach but also suggests that the nucleation free energy of the system can be perfectly described using classical nucleation theory if the Tolman length is taken into account.

Interannual variability in glacier contribution to runoff from a high‐elevation Andean catchment: Understanding the role of debris cover in glacier hydrology - Burger, Flavia; Ayala, Alvaro; Farias, David; Shaw, Thomas E.; MacDonell, Shelley; Brock, Ben; McPhee, James; Pellicciotti, Francesca (Hydrological Processes)
We present a field-data rich modelling analysis to reconstruct the climatic forcing, glacier response, and runoff generation from a high-elevation catchment in central Chile over the period 2000–2015 to provide insights into the differing contributions of debris-covered and debris-free glaciers under current and future changing climatic conditions. Model simulations with the physically based glacio-hydrological model TOPKAPI-ETH reveal a period of neutral or slightly positive mass balance between 2000 and 2010, followed by a transition to increasingly large annual mass losses, associated with a recent mega drought. Mass losses commence earlier, and are more severe, for a heavily debris-covered glacier, most likely due to its strong dependence on snow avalanche accumulation, which has declined in recent years. Catchment runoff shows a marked decreasing trend over the study period, but with high interannual variability directly linked to winter snow accumulation, and high contribution from ice melt in dry periods and drought conditions. The study demonstrates the importance of incorporating local-scale processes such as snow avalanche accumulation and spatially variable debris thickness, in understanding the responses of different glacier types to climate change. We highlight the increased dependency of runoff from high Andean catchments on the diminishing resource of glacier ice during dry years.
Keywords: Water Science and Technology

Snow depth structure, fractal behavior, and interannual consistency over Haut Glacier d'Arolla, Switzerland - Clemenzi, I.; Pellicciotti, Francesca; Burlando, P. (Water Resources Research)
Snow depth patterns over glaciers are controlled by precipitation, snow redistribution due to wind and avalanches, and the exchange of energy with the atmosphere that determines snow ablation. While many studies have advanced the understanding of ablation processes, less is known about winter snow patterns and their variability over glaciers. We analyze snow depth on Haut Glacier d'Arolla, Switzerland, in the two winter seasons 2006–2007 and 2010–2011 to (1) understand whether snow depth over an alpine glacier at the end of the accumulation season exhibits a behavior similar to the one observed on single slopes and vegetated areas; and (2) investigate the snow pattern consistency over the two accumulation seasons. We perform this analysis on a data set of high-resolution lidar-derived snow depth using variograms and fractal parameters. Our first main result is that snow depth patterns on the glacier exhibit a multiscale behavior, with a scale break around 20 m after which the fractal dimension increases, indicating more autocorrelated structure before the scale break than after. Second, this behavior is consistent over the two years, with fractal parameters and their spatial variability almost constant in the two seasons. We also show that snow depth patterns exhibit a distinct behavior in the glacier tongue and the upper catchment, with longer correlation distances on the tongue in the direction of the main winds, suggesting spatial distinctions that are likely induced by different processes and that should be taken into account when extrapolating snow depth from limited samples.
Keywords: Water Science and Technology

Surface pond energy absorption across four Himalayan Glaciers accounts for 1/8 of total catchment ice loss - Miles, Evan S.; Willis, Ian; Buri, Pascal; Steiner, Jakob F.; Arnold, Neil S.; Pellicciotti, Francesca (Geophysical Research Letters)
Glaciers in the high mountains of Asia provide an important water resource for millions of people. Many of these glaciers are partially covered by rocky debris, which protects the ice from solar radiation and warm air. However, studies have found that the surface of these debris-covered glaciers is actually lowering as fast as glaciers without debris. Water ponded on the surface of the glaciers may be partially responsible, as water can absorb atmospheric energy very efficiently. However, the overall effect of these ponds has not been thoroughly assessed yet. We study a valley in Nepal for which we have extensive weather measurements, and we use a numerical model to calculate the energy absorbed by ponds on the surface of the glaciers over 6 months. As we have not observed each individual pond thoroughly, we run the model 5,000 times with different setups. We find that ponds are extremely important for glacier melt and absorb energy 14 times as quickly as the debris-covered ice. Although the ponds account for 1% of the glacier area covered by rocks, and only 0.3% of the total glacier area, they absorb enough energy to account for one eighth of the whole valley's ice loss.
Keywords: General Earth and Planetary Sciences; Geophysics

Aspect controls the survival of ice cliffs on debris-covered glaciers - Buri, Pascal; Pellicciotti, Francesca (PNAS)
Supraglacial ice cliffs exist on debris-covered glaciers worldwide, but despite their importance as melt hot spots, their life cycle is little understood. Early field observations had advanced a hypothesis of survival of north-facing and disappearance of south-facing cliffs, which is central for predicting the contribution of cliffs to total glacier mass losses. Their role as windows of energy transfer suggests they may explain the anomalously high mass losses of debris-covered glaciers in High Mountain Asia (HMA) despite the insulating debris, currently at the center of a debated controversy. We use a 3D model of cliff evolution coupled to very high-resolution topographic data to demonstrate that ice cliffs facing south (in the Northern Hemisphere) disappear within a few months due to enhanced solar radiation receipts and that aspect is the key control on cliffs evolution. We reproduce continuous flattening of south-facing cliffs, a result of their vertical gradient of incoming solar radiation and sky view factor. Our results establish that only north-facing cliffs are recurrent features and thus stable contributors to the melting of debris-covered glaciers. Satellite observations and mass balance modeling confirms that few south-facing cliffs of small size exist on the glaciers of Langtang, and their contribution to the glacier volume losses is very small (∼1%). This has major implications for the mass balance of HMA debris-covered glaciers as it provides the basis for new parameterizations of cliff evolution and distribution to constrain volume losses in a region where glaciers are highly relevant as water sources for millions of people.

Automated detection of ice cliffs within supraglacial debris cover - Herreid, Sam; Pellicciotti, Francesca (The Cryosphere)
Ice cliffs within a supraglacial debris cover have been identified as a source for high ablation relative to the surrounding debris-covered area. Due to their small relative size and steep orientation, ice cliffs are difficult to detect using nadir-looking space borne sensors. The method presented here uses surface slopes calculated from digital elevation model (DEM) data to map ice cliff geometry and produce an ice cliff probability map. Surface slope thresholds, which can be sensitive to geographic location and/or data quality, are selected automatically. The method also attempts to include area at the (often narrowing) ends of ice cliffs which could otherwise be neglected due to signal saturation in surface slope data. The method was calibrated in the eastern Alaska Range, Alaska, USA, against a control ice cliff dataset derived from high-resolution visible and thermal data. Using the same input parameter set that performed best in Alaska, the method was tested against ice cliffs manually mapped in the Khumbu Himal, Nepal. Our results suggest the method can accommodate different glaciological settings and different DEM data sources without a data intensive (high-resolution, multi-data source) recalibration.
Keywords: Earth-Surface Processes; Water Science and Technology

Supported two-dimensional materials under ion irradiation: The substrate governs defect production - Kretschmer, Silvan; Maslov, Mikhail; Ghaderzadeh, Sadegh; Ghorbani-Asl, Mahdi; Hlawacek, Gregor; Krasheninnikov, Arkady V. (ACS Applied Materials & Interfaces)
Focused ion beams perfectly suit for patterning two-dimensional (2D) materials, but the optimization of irradiation parameters requires full microscopic understanding of defect production mechanisms. In contrast to freestanding 2D systems, the details of damage creation in supported 2D materials are not fully understood, whereas the majority of experiments have been carried out for 2D targets deposited on substrates. Here, we suggest a universal and computationally efficient scheme to model the irradiation of supported 2D materials, which combines analytical potential molecular dynamics with Monte Carlo simulations and makes it possible to independently assess the contributions to the damage from backscattered ions and atoms sputtered from the substrate. Using the scheme, we study the defect production in graphene and MoS2 sheets, which are the two most important and wide-spread 2D materials, deposited on a SiO2 substrate. For helium and neon ions with a wide range of initial ion energies including those used in a commercial helium ion microscope (HIM), we demonstrate that depending on the ion energy and mass, the defect production in 2D systems can be dominated by backscattered ions and sputtered substrate atoms rather than by the direct ion impacts and that the amount of damage in 2D materials heavily depends on whether a substrate is present or not. We also study the factors which limit the spatial resolution of the patterning process. Our results, which agree well with the available experimental data, provide not only insights into defect production but also quantitative information, which can be used for the minimization of damage during imaging in HIM or optimization of the patterning process.
Keywords: General Materials Science

Reversible photoswitching of encapsulated azobenzenes in water - Samanta, Dipak; Gemen, Julius; Chu, Zonglin; Diskin-Posner, Yael; Shimon, Linda J. W.; Klajn, Rafal (Proceedings of the National Academy of Sciences)
Efficient molecular switching in confined spaces is critical for the successful development of artificial molecular machines. However, molecular switching events often entail large structural changes and therefore require conformational freedom, which is typically limited under confinement conditions. Here, we investigated the behavior of azobenzene—the key building block of light-controlled molecular machines—in a confined environment that is flexible and can adapt its shape to that of the bound guest. To this end, we encapsulated several structurally diverse azobenzenes within the cavity of a flexible, water-soluble coordination cage, and investigated their light-responsive behavior. Using UV/Vis absorption spectroscopy and a combination of NMR methods, we showed that each of the encapsulated azobenzenes exhibited distinct switching properties. An azobenzene forming a 1:1 host–guest inclusion complex could be efficiently photoisomerized in a reversible fashion. In contrast, successful switching in inclusion complexes incorporating two azobenzene guests was dependent on the availability of free cages in the system, and it involved reversible trafficking of azobenzene between the cages. In the absence of extra cages, photoswitching was either suppressed or it involved expulsion of azobenzene from the cage and consequently its precipitation from the solution. This finding was utilized to develop an information storage medium in which messages could be written and erased in a reversible fashion using light.
Keywords: Multidisciplinary

Reversible chromism of spiropyran in the cavity of a flexible coordination cage - Samanta, Dipak; Galaktionova, Daria; Gemen, Julius; Shimon, Linda J. W.; Diskin-Posner, Yael; Avram, Liat; Král, Petr; Klajn, Rafal (Nature Communications)
Confining molecules to volumes only slightly larger than the molecules themselves can profoundly alter their properties. Molecular switches—entities that can be toggled between two or more forms upon exposure to an external stimulus—often require conformational freedom to isomerize. Therefore, placing these switches in confined spaces can render them non-operational. To preserve the switchability of these species under confinement, we work with a water-soluble coordination cage that is flexible enough to adapt its shape to the conformation of the encapsulated guest. We show that owing to its flexibility, the cage is not only capable of accommodating—and solubilizing in water—several light-responsive spiropyran-based molecular switches, but, more importantly, it also provides an environment suitable for the efficient, reversible photoisomerization of the bound guests. Our findings pave the way towards studying various molecular switching processes in confined environments.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

“Precipitation on nanoparticles”: Attractive intermolecular interactions stabilize specific ligand ratios on the surfaces of nanoparticles - Chu, Zonglin; Han, Yanxiao; Král, Petr; Klajn, Rafal (Angewandte Chemie International Edition)
Confining organic molecules to the surfaces of inorganic nanoparticles can induce intermolecular interactions between them, which can affect the composition of the mixed self-assembled monolayers obtained by co-adsorption from solution of two different molecules. Two thiolated ligands (a dialkylviologen and a zwitterionic sulfobetaine) that can interact with each other electrostatically were coadsorbed onto gold nanoparticles. The nanoparticles favor a narrow range of ratios of these two molecules that is largely independent of the molar ratio in solution. Changing the solution molar ratio of the two ligands by a factor of 5 000 affects the on-nanoparticle ratio of these ligands by only threefold. This behavior is reminiscent of the formation of insoluble inorganic salts (such as AgCl), which similarly compensate positive and negative charges upon crystallizing. Our results pave the way towards developing well-defined hybrid organic–inorganic nanostructures.
Keywords: General Chemistry; Catalysis

Dissipative self-assembly driven by the consumption of chemical fuels - De, Soumen; Klajn, Rafal (Advanced Materials)
Dissipative self-assembly leads to structures and materials that exist away from equilibrium by continuously exchanging energy and materials with the external environment. Although this mode of self-assembly is ubiquitous in nature, where it gives rise to functions such as signal processing, motility, self-healing, self-replication, and ultimately life, examples of dissipative self-assembly processes in man-made systems are few and far between. Herein, recent progress in developing diverse synthetic dissipative self-assembly systems is discussed. The systems reported thus far can be categorized into three classes, in which: i) the fuel chemically modifies the building blocks, thus triggering their self-assembly, ii) the fuel acts as a template interacting with the building blocks noncovalently, and iii) transient states are induced by the addition of two mutually exclusive stimuli. These early studies give rise to materials that would be difficult to obtain otherwise, including hydrogels with programmable lifetimes, vesicular nanoreactors, and membranes exhibiting transient conductivity.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Integrating macromolecules with molecular switches - Bléger, David; Klajn, Rafal (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Spectral models for binary products: Unifying subdwarfs and Wolf-Rayet stars as a sequence of stripped-envelope stars - Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Groh, J. H.; Kupfer, T.; Crowther, P. A.; Zapartas, E.; Renzo, M. (Astronomy & Astrophysics)
Stars stripped of their hydrogen-rich envelope through interaction with a binary companion are generally not considered when accounting for ionizing radiation from stellar populations, despite the expectation that stripped stars emit hard ionizing radiation, form frequently, and live 10–100 times longer than single massive stars. We compute the first grid of evolutionary and spectral models specially made for stars stripped in binaries for a range of progenitor masses (2–20 M⊙) and metallicities ranging from solar to values representative for pop II stars. For stripped stars with masses in the range 0.3–7 M⊙, we find consistently high effective temperatures (20 000–100 000 K, increasing with mass), small radii (0.2–1 R⊙), and high bolometric luminosities, comparable to that of their progenitor before stripping. The spectra show a continuous sequence that naturally bridges subdwarf-type stars at the low-mass end and Wolf-Rayet-like spectra at the high-mass end. For intermediate masses we find hybrid spectral classes showing a mixture of absorption and emission lines. These appear for stars with mass-loss rates of 10−8−10−6 M⊙ yr−1, which have semi-transparent atmospheres. At low metallicity, substantial hydrogen-rich layers are left at the surface and we predict spectra that resemble O-type stars instead. We obtain spectra undistinguishable from subdwarfs for stripped stars with masses up to 1.7 M⊙, which questions whether the widely adopted canonical value of 0.47 M⊙ is uniformly valid. Only a handful of stripped stars of intermediate mass have currently been identified observationally. Increasing this sample will provide necessary tests for the physics of interaction, internal mixing, and stellar winds. We use our model spectra to investigate the feasibility to detect stripped stars next to an optically bright companion and recommend systematic searches for their UV excess and possible emission lines, most notably HeII λ4686 in the optical and HeII λ1640 in the UV. Our models are publicly available for further investigations or inclusion in spectral synthesis simulations.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Clues about the scarcity of stripped-envelope stars from the evolutionary state of the sdO+Be binary system φ Persei - Schootemeijer, A.; Götberg, Ylva Louise Linsdotter; de Mink, S. E.; Gies, D.; Zapartas, E. (Astronomy & Astrophysics)
Stripped-envelope stars form in binary systems after losing mass through Roche-lobe overflow. They bear astrophysical significance as sources of UV and ionizing radiation in older stellar populations and, if sufficiently massive, as stripped supernova progenitors. Binary evolutionary models predict that they are common, but only a handful of subdwarfs with B-type companions are known. The question is whether a large population of such systems has evaded detection as a result of biases, or whether the model predictions are wrong. We reanalyze the well-studied post-interaction binary φ Persei. Recently, new data have improved the orbital solution of the system, which contains an ~1.2M⊙ stripped-envelope star and a rapidly rotating ~9.6M⊙ Be star. We compare with an extensive grid of evolutionary models using a Bayesian approach and constrain the initial masses of the progenitor to 7.2 ± 0.4M⊙ for the stripped star and 3.8 ± 0.4M⊙ for the Be star. The system must have evolved through near-conservative mass transfer. These findings are consistent with earlier studies. The age we obtain, 57 ± 9 Myr, is in excellent agreement with the age of the α Persei cluster. We note that neither star was initially massive enough to produce a core-collapse supernova, but mass exchange pushed the Be star above the mass threshold. We find that the subdwarf is overluminous for its mass by almost an order of magnitude, compared to the expectations for a helium core burning star. We can only reconcile this if the subdwarf resides in a late phase of helium shell burning, which lasts only 2–3% of the total lifetime as a subdwarf. Assuming continuous star formation implies that up to ~50 less evolved, dimmer subdwarfs exist for each system similar to φ Persei, but have evaded detection so far. Our findings can be interpreted as a strong indication that a substantial population of stripped-envelope stars indeed exists, but has so far evaded detection because of observational biases and lack of large-scale systematic searches.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Extreme isolation of WN3/O3 stars and implications for their evolutionary origin as the elusive stripped binaries - Smith, Nathan; Götberg, Ylva Louise Linsdotter; de Mink, Selma E (Monthly Notices of the Royal Astronomical Society)
Recent surveys of the Magellanic Clouds have revealed a subtype of Wolf–Rayet (WR) star with peculiar properties. WN3/O3 spectra exhibit both WR-like emission and O3 V-like absorption – but at lower luminosity than O3 V or WN stars. We examine the projected spatial distribution of WN3/O3 stars in the Large Magellanic Cloud as compared to O-type stars. Surprisingly, WN3/O3 stars are among the most isolated of all classes of massive stars; they have a distribution similar to red supergiants dominated by initial masses of 10–15 M⊙, and are far more dispersed than classical WR stars or luminous blue variables. Their lack of association with clusters of O-type stars suggests strongly that WN3/O3 stars are not the descendants of single massive stars (30 M⊙ or above). Instead, they are likely products of interacting binaries at lower initial mass (10–18 M⊙). Comparison with binary models suggests a probable origin with primaries in this mass range that were stripped of their H envelopes through non-conservative mass transfer by a low-mass secondary. We show that model spectra and positions on the Hertzsprung–Russell diagram for binary-stripped stars are consistent with WN3/O3 stars. Monitoring radial velocities with high-resolution spectra can test for low-mass companions or runaway velocities. With lower initial mass and environments that avoid very massive stars, the WN3/O3 stars fit expectations for progenitors of Type Ib and possibly Type Ibn supernovae.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The ℤ2-Genus of Kuratowski minors - Fulek, Radoslav; Kynčl, Jan
A drawing of a graph on a surface is independently even if every pair of nonadjacent edges in the drawing crosses an even number of times. The ℤ2-genus of a graph G is the minimum g such that G has an independently even drawing on the orientable surface of genus g. An unpublished result by Robertson and Seymour implies that for every t, every graph of sufficiently large genus contains as a minor a projective t × t grid or one of the following so-called t-Kuratowski graphs: K3, t, or t copies of K5 or K3,3 sharing at most 2 common vertices. We show that the ℤ2-genus of graphs in these families is unbounded in t; in fact, equal to their genus. Together, this implies that the genus of a graph is bounded from above by a function of its ℤ2-genus, solving a problem posed by Schaefer and Štefankovič, and giving an approximate version of the Hanani-Tutte theorem on orientable surfaces.

Chiral discrimination through bielliptical high-harmonic spectroscopy - Baykusheva, Denitsa Rangelova; Wörner, Hans Jakob (Physical Review X)
Molecular chirality plays an essential role in most biochemical processes. The observation and quantification of chirality-sensitive signals, however, remains extremely challenging, especially on ultrafast timescales and in dilute media. Here, we describe the experimental realization of an all-optical and ultrafast scheme for detecting chiral dynamics in molecules. This technique is based on high-harmonic generation by a combination of two-color counterrotating femtosecond laser pulses with polarization states tunable from linear to circular. We demonstrate two different implementations of chiral-sensitive high-harmonic spectroscopy on an ensemble of randomly oriented methyloxirane molecules in the gas phase. Using two elliptically polarized fields, we observe that the ellipticities maximizing the harmonic signal reach up to 4.4 ± 0.2 % (at 17.6 eV). Using two circularly polarized fields, we observe circular dichroisms ranging up to 13 ± 6 % (28.3–33.1 eV). Our theoretical analysis confirms that the observed chiral response originates from subfemtosecond electron dynamics driven by the magnetic component of the driving laser field. This assignment is supported by the experimental observation of a strong intensity dependence of the chiral effects and its agreement with theory. We moreover report and explain a pronounced variation of the signal strength and dichroism with the driving-field ellipticities and harmonic orders. Finally, we demonstrate the sensitivity of the experimental observables to the shape of the electron hole. This technique for chiral discrimination will yield femtosecond temporal resolution when integrated in a pump-probe scheme and subfemtosecond resolution on chiral charge migration in a self-probing scheme.
Keywords: General Physics and Astronomy

Thrackles: An improved upper bound - Fulek, Radoslav; Pach, János
A thrackle is a graph drawn in the plane so that every pair of its edges meet exactly once: either at a common end vertex or in a proper crossing. We prove that any thrackle of n vertices has at most 1.3984n edges. Quasi-thrackles are defined similarly, except that every pair of edges that do not share a vertex are allowed to cross an odd number of times. It is also shown that the maximum number of edges of a quasi-thrackle on n vertices is 3/2(n-1), and that this bound is best possible for infinitely many values of n.

Data from: Multiple chromosomal rearrangements in a hybrid zone between Littorina saxatilis ecotypes - Faria, Rui; Chaube, Pragya; Morales, Hernán E.; Larsson, Tomas; Lemmon, Alan R.; Lemmon, Emily M.; Rafajlović, Marina; Panova, Marina; Ravinet, Mark; Johannesson, Kerstin; Westram, Anja M; Butlin, Roger K.
Both classical and recent studies suggest that chromosomal inversion polymorphisms are important in adaptation and speciation. However, biases in discovery and reporting of inversions make it difficult to assess their prevalence and biological importance. Here, we use an approach based on linkage disequilibrium among markers genotyped for samples collected across a transect between contrasting habitats to detect chromosomal rearrangements de novo. We report 17 polymorphic rearrangements in a single locality for the coastal marine snail, Littorina saxatilis. Patterns of diversity in the field and of recombination in controlled crosses provide strong evidence that at least the majority of these rearrangements are inversions. Most show clinal changes in frequency between habitats, suggestive of divergent selection, but only one appears to be fixed for different arrangements in the two habitats. Consistent with widespread evidence for balancing selection on inversion polymorphisms, we argue that a combination of heterosis and divergent selection can explain the observed patterns and should be considered in other systems spanning environmental gradients.

Cost analysis of nondeterministic probabilistic programs - Anonymous, 1; Anonymous, 2; Anonymous, 3; Anonymous, 4; Anonymous, 5; Anonymous, 6
We consider the problem of expected cost analysis over nondeterministic probabilistic programs, which aims at automated methods for analyzing the resource-usage of such programs. Previous approaches for this problem could only handle nonnegative bounded costs. However, in many scenarios, such as queuing networks or analysis of cryptocurrency protocols, both positive and negative costs are necessary and the costs are unbounded as well. In this work, we present a sound and efficient approach to obtain polynomial bounds on the expected accumulated cost of nondeterministic probabilistic programs. Our approach can handle (a) general positive and negative costs with bounded updates in variables; and (b) nonnegative costs with general updates to variables. We show that several natural examples which could not be handled by previous approaches are captured in our framework. Moreover, our approach leads to an efficient polynomial-time algorithm, while no previous approach for cost analysis of probabilistic programs could guarantee polynomial runtime. Finally, we show the effectiveness of our approach by presenting experimental results on a variety of programs, motivated by real-world applications, for which we efficiently synthesize tight resource-usage bounds.

Absorption and directed Jónsson terms - Kazda, Alexandr; Kozik, Marcin; McKenzie, Ralph; Moore, Matthew (Don Pigozzi on Abstract Algebraic Logic, Universal Algebra, and Computer Science)
We prove that every congruence distributive variety has directed Jónsson terms, and every congruence modular variety has directed Gumm terms. The directed terms we construct witness every case of absorption witnessed by the original Jónsson or Gumm terms. This result is equivalent to a pair of claims about absorption for admissible preorders in congruence distributive and congruence modular varieties, respectively. For finite algebras, these absorption theorems have already seen significant applications, but until now, it was not clear if the theorems hold for general algebras as well. Our method also yields a novel proof of a result by P. Lipparini about the existence of a chain of terms (which we call Pixley terms) in varieties that are at the same time congruence distributive and k-permutable for some k.

Shellability is NP-complete - Goaoc, Xavier; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli
We prove that for every d ≥ 2, deciding if a pure, d-dimensional, simplicial complex is shellable is NP-hard, hence NP-complete. This resolves a question raised, e.g., by Danaraj and Klee in 1978. Our reduction also yields that for every d ≥ 2 and k ≥ 0, deciding if a pure, d-dimensional, simplicial complex is k-decomposable is NP-hard. For d ≥ 3, both problems remain NP-hard when restricted to contractible pure d-dimensional complexes.

On the treewidth of triangulated 3-manifolds - Huszár, Kristóf; Spreer, Jonathan; Wagner, Uli
In graph theory, as well as in 3-manifold topology, there exist several width-type parameters to describe how "simple" or "thin" a given graph or 3-manifold is. These parameters, such as pathwidth or treewidth for graphs, or the concept of thin position for 3-manifolds, play an important role when studying algorithmic problems; in particular, there is a variety of problems in computational 3-manifold topology - some of them known to be computationally hard in general - that become solvable in polynomial time as soon as the dual graph of the input triangulation has bounded treewidth. In view of these algorithmic results, it is natural to ask whether every 3-manifold admits a triangulation of bounded treewidth. We show that this is not the case, i.e., that there exists an infinite family of closed 3-manifolds not admitting triangulations of bounded pathwidth or treewidth (the latter implies the former, but we present two separate proofs). We derive these results from work of Agol and of Scharlemann and Thompson, by exhibiting explicit connections between the topology of a 3-manifold M on the one hand and width-type parameters of the dual graphs of triangulations of M on the other hand, answering a question that had been raised repeatedly by researchers in computational 3-manifold topology. In particular, we show that if a closed, orientable, irreducible, non-Haken 3-manifold M has a triangulation of treewidth (resp. pathwidth) k then the Heegaard genus of M is at most 48(k+1) (resp. 4(3k+1)).

Fast and accurate large multiple sequence alignments with a root-to-leaf regressive method - Garriga, Edgar; di Tommaso, Paolo; Magis, Cedrik; Erb, Ionas; Mansouri, Leila; Baltzis, Athanasios; Laayouni, Hafid; Kondrashov, Fyodor; Floden, Evan; Notredame, Cedric
This dataset contains a GitHub repository containing all the data, analysis, Nextflow workflows and Jupyter notebooks to replicate the manuscript titled "Fast and accurate large multiple sequence alignments with a root-to-leaf regressive method". It also contains the Multiple Sequence Alignments (MSAs) generated and well as the main figures and tables from the manuscript. The repository is also available at GitHub (https://github.com/cbcrg/dpa-analysis) release `v1.2`. For details on how to use the regressive alignment algorithm, see the T-Coffee software suite (https://github.com/cbcrg/tcoffee).

Ge hut wires - from growth to hole spin resonance - Watzinger, Hannes
Nowadays, quantum computation is receiving more and more attention as an alternative to the classical way of computing. For realizing a quantum computer, different devices are investigated as potential quantum bits. In this thesis, the focus is on Ge hut wires, which turned out to be promising candidates for implementing hole spin quantum bits. The advantages of Ge as a material system are the low hyperfine interaction for holes and the strong spin orbit coupling, as well as the compatibility with the highly developed CMOS processes in industry. In addition, Ge can also be isotopically purified which is expected to boost the spin coherence times. The strong spin orbit interaction for holes in Ge on the one hand enables the full electrical control of the quantum bit and on the other hand should allow short spin manipulation times. Starting with a bare Si wafer, this work covers the entire process reaching from growth over the fabrication and characterization of hut wire devices up to the demonstration of hole spin resonance. From experiments with single quantum dots, a large g-factor anisotropy between the in-plane and the out-of-plane direction was found. A comparison to a theoretical model unveiled the heavy-hole character of the lowest energy states. The second part of the thesis addresses double quantum dot devices, which were realized by adding two gate electrodes to a hut wire. In such devices, Pauli spin blockade was observed, which can serve as a read-out mechanism for spin quantum bits. Applying oscillating electric fields in spin blockade allowed the demonstration of continuous spin rotations and the extraction of a lower bound for the spin dephasing time. Despite the strong spin orbit coupling in Ge, the obtained value for the dephasing time is comparable to what has been recently reported for holes in Si. All in all, the presented results point out the high potential of Ge hut wires as a platform for long-lived, fast and fully electrically tunable hole spin quantum bits.

Multiple covers with balls - Iglesias Ham, Mabel
We describe arrangements of three-dimensional spheres from a geometrical and topological point of view. Real data (fitting this setup) often consist of soft spheres which show certain degree of deformation while strongly packing against each other. In this context, we answer the following questions: If we model a soft packing of spheres by hard spheres that are allowed to overlap, can we measure the volume in the overlapped areas? Can we be more specific about the overlap volume, i.e. quantify how much volume is there covered exactly twice, three times, or k times? What would be a good optimization criteria that rule the arrangement of soft spheres while making a good use of the available space? Fixing a particular criterion, what would be the optimal sphere configuration? The first result of this thesis are short formulas for the computation of volumes covered by at least k of the balls. The formulas exploit information contained in the order-k Voronoi diagrams and its closely related Level-k complex. The used complexes lead to a natural generalization into poset diagrams, a theoretical formalism that contains the order-k and degree-k diagrams as special cases. In parallel, we define different criteria to determine what could be considered an optimal arrangement from a geometrical point of view. Fixing a criterion, we find optimal soft packing configurations in 2D and 3D where the ball centers lie on a lattice. As a last step, we use tools from computational topology on real physical data, to show the potentials of higher-order diagrams in the description of melting crystals. The results of the experiments leaves us with an open window to apply the theories developed in this thesis in real applications.

Learning from dependent data - Zimin, Alexander
The most common assumption made in statistical learning theory is the assumption of the independent and identically distributed (i.i.d.) data. While being very convenient mathematically, it is often very clearly violated in practice. This disparity between the machine learning theory and applications underlies a growing demand in the development of algorithms that learn from dependent data and theory that can provide generalization guarantees similar to the independent situations. This thesis is dedicated to two variants of dependencies that can arise in practice. One is a dependence on the level of samples in a single learning task. Another dependency type arises in the multi-task setting when the tasks are dependent on each other even though the data for them can be i.i.d. In both cases we model the data (samples or tasks) as stochastic processes and introduce new algorithms for both settings that take into account and exploit the resulting dependencies. We prove the theoretical guarantees on the performance of the introduced algorithms under different evaluation criteria and, in addition, we compliment the theoretical study by the empirical one, where we evaluate some of the algorithms on two real world datasets to highlight their practical applicability.

Proof systems for sustainable decentralized cryptocurrencies - Abusalah, Hamza M
A proof system is a protocol between a prover and a verifier over a common input in which an honest prover convinces the verifier of the validity of true statements. Motivated by the success of decentralized cryptocurrencies, exemplified by Bitcoin, the focus of this thesis will be on proof systems which found applications in some sustainable alternatives to Bitcoin, such as the Spacemint and Chia cryptocurrencies. In particular, we focus on proofs of space and proofs of sequential work. Proofs of space (PoSpace) were suggested as more ecological, economical, and egalitarian alternative to the energy-wasteful proof-of-work mining of Bitcoin. However, the state-of-the-art constructions of PoSpace are based on sophisticated graph pebbling lower bounds, and are therefore complex. Moreover, when these PoSpace are used in cryptocurrencies like Spacemint, miners can only start mining after ensuring that a commitment to their space is already added in a special transaction to the blockchain. Proofs of sequential work (PoSW) are proof systems in which a prover, upon receiving a statement x and a time parameter T, computes a proof which convinces the verifier that T time units had passed since x was received. Whereas Spacemint assumes synchrony to retain some interesting Bitcoin dynamics, Chia requires PoSW with unique proofs, i.e., PoSW in which it is hard to come up with more than one accepting proof for any true statement. In this thesis we construct simple and practically-efficient PoSpace and PoSW. When using our PoSpace in cryptocurrencies, miners can start mining on the fly, like in Bitcoin, and unlike current constructions of PoSW, which either achieve efficient verification of sequential work, or faster-than-recomputing verification of correctness of proofs, but not both at the same time, ours achieve the best of these two worlds.

Weakly-Supervised Segmentation and Unsupervised Modeling of Natural Images - Kolesnikov, Alexander
Modern computer vision systems heavily rely on statistical machine learning models, which typically require large amounts of labeled data to be learned reliably. Moreover, very recently computer vision research widely adopted techniques for representation learning, which further increase the demand for labeled data. However, for many important practical problems there is relatively small amount of labeled data available, so it is problematic to leverage full potential of the representation learning methods. One way to overcome this obstacle is to invest substantial resources into producing large labelled datasets. Unfortunately, this can be prohibitively expensive in practice. In this thesis we focus on the alternative way of tackling the aforementioned issue. We concentrate on methods, which make use of weakly-labeled or even unlabeled data. Specifically, the first half of the thesis is dedicated to the semantic image segmentation task. We develop a technique, which achieves competitive segmentation performance and only requires annotations in a form of global image-level labels instead of dense segmentation masks. Subsequently, we present a new methodology, which further improves segmentation performance by leveraging tiny additional feedback from a human annotator. By using our methods practitioners can greatly reduce the amount of data annotation effort, which is required to learn modern image segmentation models. In the second half of the thesis we focus on methods for learning from unlabeled visual data. We study a family of autoregressive models for modeling structure of natural images and discuss potential applications of these models. Moreover, we conduct in-depth study of one of these applications, where we develop the state-of-the-art model for the probabilistic image colorization task.

Computing simplicial representatives of homotopy group elements - Filakovský, Marek; Franek, Peter; Wagner, Uli; Zhechev, Stephan Y (Journal of Applied and Computational Topology)
A central problem of algebraic topology is to understand the homotopy groups 𝜋𝑑(𝑋) of a topological space X. For the computational version of the problem, it is well known that there is no algorithm to decide whether the fundamental group 𝜋1(𝑋) of a given finite simplicial complex X is trivial. On the other hand, there are several algorithms that, given a finite simplicial complex X that is simply connected (i.e., with 𝜋1(𝑋) trivial), compute the higher homotopy group 𝜋𝑑(𝑋) for any given 𝑑≥2 . However, these algorithms come with a caveat: They compute the isomorphism type of 𝜋𝑑(𝑋) , 𝑑≥2 as an abstract finitely generated abelian group given by generators and relations, but they work with very implicit representations of the elements of 𝜋𝑑(𝑋) . Converting elements of this abstract group into explicit geometric maps from the d-dimensional sphere 𝑆𝑑 to X has been one of the main unsolved problems in the emerging field of computational homotopy theory. Here we present an algorithm that, given a simply connected space X, computes 𝜋𝑑(𝑋) and represents its elements as simplicial maps from a suitable triangulation of the d-sphere 𝑆𝑑 to X. For fixed d, the algorithm runs in time exponential in size(𝑋) , the number of simplices of X. Moreover, we prove that this is optimal: For every fixed 𝑑≥2 , we construct a family of simply connected spaces X such that for any simplicial map representing a generator of 𝜋𝑑(𝑋) , the size of the triangulation of 𝑆𝑑 on which the map is defined, is exponential in size(𝑋) .

Synchronizing the asynchronous - Kragl, Bernhard; Qadeer, Shaz; Henzinger, Thomas A
Synchronous programs are easy to specify because the side effects of an operation are finished by the time the invocation of the operation returns to the caller. Asynchronous programs, on the other hand, are difficult to specify because there are side effects due to pending computation scheduled as a result of the invocation of an operation. They are also difficult to verify because of the large number of possible interleavings of concurrent computation threads. We present synchronization, a new proof rule that simplifies the verification of asynchronous programs by introducing the fiction, for proof purposes, that asynchronous operations complete synchronously. Synchronization summarizes an asynchronous computation as immediate atomic effect. Modular verification is enabled via pending asynchronous calls in atomic summaries, and a complementary proof rule that eliminates pending asynchronous calls when components and their specifications are composed. We evaluate synchronization in the context of a multi-layer refinement verification methodology on a collection of benchmark programs.

The multi-cover persistence of Euclidean balls - Edelsbrunner, Herbert; Osang, Georg F
Given a locally finite X ⊆ ℝd and a radius r ≥ 0, the k-fold cover of X and r consists of all points in ℝd that have k or more points of X within distance r. We consider two filtrations - one in scale obtained by fixing k and increasing r, and the other in depth obtained by fixing r and decreasing k - and we compute the persistence diagrams of both. While standard methods suffice for the filtration in scale, we need novel geometric and topological concepts for the filtration in depth. In particular, we introduce a rhomboid tiling in ℝd+1 whose horizontal integer slices are the order-k Delaunay mosaics of X, and construct a zigzag module from Delaunay mosaics that is isomorphic to the persistence module of the multi-covers.

3-Webs generated by confocal conics and circles - Akopyan, Arseniy (Geometriae Dedicata)
We consider families of confocal conics and two pencils of Apollonian circles having the same foci. We will show that these families of curves generate trivial 3-webs and find the exact formulas describing them.

A germanium hole spin qubit - Watzinger, Hannes; Kukucka, Josip; Vukusic, Lada; Gao, Fei; Wang, Ting; Schäffler, Friedrich; Zhang, Jian; Katsaros, Georgios (Nature Communications)
Holes confined in quantum dots have gained considerable interest in the past few years due to their potential as spin qubits. Here we demonstrate two-axis control of a spin 3/2 qubit in natural Ge. The qubit is formed in a hut wire double quantum dot device. The Pauli spin blockade principle allowed us to demonstrate electric dipole spin resonance by applying a radio frequency electric field to one of the electrodes defining the double quantum dot. Coherent hole spin oscillations with Rabi frequencies reaching 140 MHz are demonstrated and dephasing times of 130 ns are measured. The reported results emphasize the potential of Ge as a platform for fast and electrically tunable hole spin qubit devices.

A biochemical network controlling basal myosin oscillation - Qin, Xiang; Hannezo, Edouard B; Mangeat, Thomas; Liu, Chang; Majumder, Pralay; Liu, Jjiaying; Choesmel Cadamuro, Valerie; Mcdonald, Jocelyn; Liu, Yinyao; Yi, Bin; Wang, Xiaobo (Nature Communications)
The actomyosin cytoskeleton, a key stress-producing unit in epithelial cells, oscillates spontaneously in a wide variety of systems. Although much of the signal cascade regulating myosin activity has been characterized, the origin of such oscillatory behavior is still unclear. Here, we show that basal myosin II oscillation in Drosophila ovarian epithelium is not controlled by actomyosin cortical tension, but instead relies on a biochemical oscillator involving ROCK and myosin phosphatase. Key to this oscillation is a diffusive ROCK flow, linking junctional Rho1 to medial actomyosin cortex, and dynamically maintained by a self-activation loop reliant on ROCK kinase activity. In response to the resulting myosin II recruitment, myosin phosphatase is locally enriched and shuts off ROCK and myosin II signals. Coupling Drosophila genetics, live imaging, modeling, and optogenetics, we uncover an intrinsic biochemical oscillator at the core of myosin II regulatory network, shedding light on the spatio-temporal dynamics of force generation.

A fat lot of good for wound healing - Casano, Alessandra M; Sixt, Michael K (Developmental Cell)
The insect’s fat body combines metabolic and immunological functions. In this issue of Developmental Cell, Franz et al. (2018) show that in Drosophila, cells of the fat body are not static, but can actively “swim” toward sites of epithelial injury, where they physically clog the wound and locally secrete antimicrobial peptides.

A micro-CT-based method for quantitative brain lesion characterization and electrode localization - Masís, Javier; Mankus, David; Wolff, Steffen; Guitchounts, Grigori; Jösch, Maximilian A; Cox, David (Scientific Reports)
Lesion verification and quantification is traditionally done via histological examination of sectioned brains, a time-consuming process that relies heavily on manual estimation. Such methods are particularly problematic in posterior cortical regions (e.g. visual cortex), where sectioning leads to significant damage and distortion of tissue. Even more challenging is the post hoc localization of micro-electrodes, which relies on the same techniques, suffers from similar drawbacks and requires even higher precision. Here, we propose a new, simple method for quantitative lesion characterization and electrode localization that is less labor-intensive and yields more detailed results than conventional methods. We leverage staining techniques standard in electron microscopy with the use of commodity micro-CT imaging. We stain whole rat and zebra finch brains in osmium tetroxide, embed these in resin and scan entire brains in a micro-CT machine. The scans result in 3D reconstructions of the brains with section thickness dependent on sample size (12–15 and 5–6 microns for rat and zebra finch respectively) that can be segmented manually or automatically. Because the method captures the entire intact brain volume, comparisons within and across studies are more tractable, and the extent of lesions and electrodes may be studied with higher accuracy than with current methods.

An armadillo-domain protein participates in a telomerase interaction network - Dokládal, Ladislav; Benková, Eva; Honys, David; Dupláková, Nikoleta; Lee, Lan; Gelvin, Stanton; Sýkorová, Eva (Plant Molecular Biology)
Arabidopsis and human ARM protein interact with telomerase. Deregulated mRNA levels of DNA repair and ribosomal protein genes in an Arabidopsis arm mutant suggest non-telomeric ARM function. The human homolog ARMC6 interacts with hTRF2. Abstract: Telomerase maintains telomeres and has proposed non-telomeric functions. We previously identified interaction of the C-terminal domain of Arabidopsis telomerase reverse transcriptase (AtTERT) with an armadillo/β-catenin-like repeat (ARM) containing protein. Here we explore protein–protein interactions of the ARM protein, AtTERT domains, POT1a, TRF-like family and SMH family proteins, and the chromatin remodeling protein CHR19 using bimolecular fluorescence complementation (BiFC), yeast two-hybrid (Y2H) analysis, and co-immunoprecipitation. The ARM protein interacts with both the N- and C-terminal domains of AtTERT in different cellular compartments. ARM interacts with CHR19 and TRF-like I family proteins that also bind AtTERT directly or through interaction with POT1a. The putative human ARM homolog co-precipitates telomerase activity and interacts with hTRF2 protein in vitro. Analysis of Arabidopsis arm mutants shows no obvious changes in telomere length or telomerase activity, suggesting that ARM is not essential for telomere maintenance. The observed interactions with telomerase and Myb-like domain proteins (TRF-like family I) may therefore reflect possible non-telomeric functions. Transcript levels of several DNA repair and ribosomal genes are affected in arm mutants, and ARM, likely in association with other proteins, suppressed expression of XRCC3 and RPSAA promoter constructs in luciferase reporter assays. In conclusion, ARM can participate in non-telomeric functions of telomerase, and can also perform its own telomerase-independent functions.

AMT 2.0: Qualitative and quantitative trace analysis with extended signal temporal logic - Nickovic, Dejan; Lebeltel, Olivier; Maler, Oded; Ferrere, Thomas; Ulus, Dogan
We introduce in this paper AMT 2.0 , a tool for qualitative and quantitative analysis of hybrid continuous and Boolean signals that combine numerical values and discrete events. The evaluation of the signals is based on rich temporal specifications expressed in extended Signal Temporal Logic (xSTL), which integrates Timed Regular Expressions (TRE) within Signal Temporal Logic (STL). The tool features qualitative monitoring (property satisfaction checking), trace diagnostics for explaining and justifying property violations and specification-driven measurement of quantitative features of the signal.

Ants avoid superinfections by performing risk-adjusted sanitary care - Konrad, Matthias; Pull, Christopher; Metzler, Sina; Seif, Katharina; Naderlinger, Elisabeth; Grasse, Anna V; Cremer, Sylvia (PNAS)
Being cared for when sick is a benefit of sociality that can reduce disease and improve survival of group members. However, individuals providing care risk contracting infectious diseases themselves. If they contract a low pathogen dose, they may develop low-level infections that do not cause disease but still affect host immunity by either decreasing or increasing the host’s vulnerability to subsequent infections. Caring for contagious individuals can thus significantly alter the future disease susceptibility of caregivers. Using ants and their fungal pathogens as a model system, we tested if the altered disease susceptibility of experienced caregivers, in turn, affects their expression of sanitary care behavior. We found that low-level infections contracted during sanitary care had protective or neutral effects on secondary exposure to the same (homologous) pathogen but consistently caused high mortality on superinfection with a different (heterologous) pathogen. In response to this risk, the ants selectively adjusted the expression of their sanitary care. Specifically, the ants performed less grooming and more antimicrobial disinfection when caring for nestmates contaminated with heterologous pathogens compared with homologous ones. By modulating the components of sanitary care in this way the ants acquired less infectious particles of the heterologous pathogens, resulting in reduced superinfection. The performance of risk-adjusted sanitary care reveals the remarkable capacity of ants to react to changes in their disease susceptibility, according to their own infection history and to flexibly adjust collective care to individual risk.

Anyonic statistics of quantum impurities in two dimensions - Yakaboylu, Enderalp; Lemeshko, Mikhail (Physical Review B - Condensed Matter and Materials Physics)
We demonstrate that identical impurities immersed in a two-dimensional many-particle bath can be viewed as flux-tube-charged-particle composites described by fractional statistics. In particular, we find that the bath manifests itself as an external magnetic flux tube with respect to the impurities, and hence the time-reversal symmetry is broken for the effective Hamiltonian describing the impurities. The emerging flux tube acts as a statistical gauge field after a certain critical coupling. This critical coupling corresponds to the intersection point between the quasiparticle state and the phonon wing, where the angular momentum is transferred from the impurity to the bath. This amounts to a novel configuration with emerging anyons. The proposed setup paves the way to realizing anyons using electrons interacting with superfluid helium or lattice phonons, as well as using atomic impurities in ultracold gases.

A theory of register monitors - Ferrere, Thomas; Henzinger, Thomas A; Saraç, Ege
The task of a monitor is to watch, at run-time, the execution of a reactive system, and signal the occurrence of a safety violation in the observed sequence of events. While finite-state monitors have been studied extensively, in practice, monitoring software also makes use of unbounded memory. We define a model of automata equipped with integer-valued registers which can execute only a bounded number of instructions between consecutive events, and thus can form the theoretical basis for the study of infinite-state monitors. We classify these register monitors according to the number k of available registers, and the type of register instructions. In stark contrast to the theory of computability for register machines, we prove that for every k 1, monitors with k + 1 counters (with instruction set 〈+1, =〉) are strictly more expressive than monitors with k counters. We also show that adder monitors (with instruction set 〈1, +, =〉) are strictly more expressive than counter monitors, but are complete for monitoring all computable safety -languages for k = 6. Real-time monitors are further required to signal the occurrence of a safety violation as soon as it occurs. The expressiveness hierarchy for counter monitors carries over to real-time monitors. We then show that 2 adders cannot simulate 3 counters in real-time. Finally, we show that real-time adder monitors with inequalities are as expressive as real-time Turing machines.

Auxin methylation is required for differential growth in Arabidopsis - Abbas, Mohamad; Hernández, García J; Pollmann, Stephan; Samodelov, Sophia L; Kolb, Martina; Friml, Jirí; Hammes, Ulrich Z; Zurbriggen, Matias D; Blázquez, Miguel; Alabadí, David (PNAS)
Asymmetric auxin distribution is instrumental for the differential growth that causes organ bending on tropic stimuli and curvatures during plant development. Local differences in auxin concentrations are achieved mainly by polarized cellular distribution of PIN auxin transporters, but whether other mechanisms involving auxin homeostasis are also relevant for the formation of auxin gradients is not clear. Here we show that auxin methylation is required for asymmetric auxin distribution across the hypocotyl, particularly during its response to gravity. We found that loss-of-function mutants in Arabidopsis IAA CARBOXYL METHYLTRANSFERASE1 (IAMT1) prematurely unfold the apical hook, and that their hypocotyls are impaired in gravitropic reorientation. This defect is linked to an auxin-dependent increase in PIN gene expression, leading to an increased polar auxin transport and lack of asymmetric distribution of PIN3 in the iamt1 mutant. Gravitropic reorientation in the iamt1 mutant could be restored with either endodermis-specific expression of IAMT1 or partial inhibition of polar auxin transport, which also results in normal PIN gene expression levels. We propose that IAA methylation is necessary in gravity-sensing cells to restrict polar auxin transport within the range of auxin levels that allow for differential responses.

Calculation of the critical temperature of a dilute Bose gas in the Bogoliubov approximation - Napiórkowski, Marcin M; Reuvers, Robin; Solovej, Jan (EPL)
Following an earlier calculation in 3D, we calculate the 2D critical temperature of a dilute, translation-invariant Bose gas using a variational formulation of the Bogoliubov approximation introduced by Critchley and Solomon in 1976. This provides the first analytical calculation of the Kosterlitz-Thouless transition temperature that includes the constant in the logarithm.

CLE9 peptide-induced stomatal closure is mediated by abscisic acid, hydrogen peroxide, and nitric oxide in arabidopsis thaliana - Zhang, Luosha; Shi, Xiong; Zhang, Yutao; Wang, Jiajing; Yang, Jingwei; Ishida, Takashi; Jiang, Wenqian; Han, Xiangyu; Kang, Jingke; Wang, Xuening; Pan, Lixia; Lv, Shuo; et al. (Plant Cell and Environment)
CLE peptides have been implicated in various developmental processes of plants and mediate their responses to environmental stimuli. However, the biological relevance of most CLE genes remains to be functionally characterized. Here, we report that CLE9, which is expressed in stomata, acts as an essential regulator in the induction of stomatal closure. Exogenous application of CLE9 peptides or overexpression of CLE9 effectively led to stomatal closure and enhanced drought tolerance, whereas CLE9 loss-of-function mutants were sensitivity to drought stress. CLE9-induced stomatal closure was impaired in abscisic acid (ABA)-deficient mutants, indicating that ABA is required for CLE9-medaited guard cell signalling. We further deciphered that two guard cell ABA-signalling components, OST1 and SLAC1, were responsible for CLE9-induced stomatal closure. MPK3 and MPK6 were activated by the CLE9 peptide, and CLE9 peptides failed to close stomata in mpk3 and mpk6 mutants. In addition, CLE9 peptides stimulated the induction of hydrogen peroxide (H2O2) and nitric oxide (NO) synthesis associated with stomatal closure, which was abolished in the NADPH oxidase-deficient mutants or nitric reductase mutants, respectively. Collectively, our results reveal a novel ABA-dependent function of CLE9 in the regulation of stomatal apertures, thereby suggesting a potential role of CLE9 in the stress acclimatization of plants.

Clonal analysis of Notch1-expressing cells reveals the existence of unipotent stem cells that retain long-term plasticity in the embryonic mammary gland - Lilja, Anna; Rodilla, Veronica; Huyghe, Mathilde; Hannezo, Edouard B; Landragin, Camille; Renaud, Olivier; Leroy, Olivier; Rulands, Steffen; Simons, Benjamin; Fré, Silvia (Nature Cell Biology)
Recent lineage tracing studies have revealed that mammary gland homeostasis relies on unipotent stem cells. However, whether and when lineage restriction occurs during embryonic mammary development, and which signals orchestrate cell fate specification, remain unknown. Using a combination of in vivo clonal analysis with whole mount immunofluorescence and mathematical modelling of clonal dynamics, we found that embryonic multipotent mammary cells become lineage-restricted surprisingly early in development, with evidence for unipotency as early as E12.5 and no statistically discernable bipotency after E15.5. To gain insights into the mechanisms governing the switch from multipotency to unipotency, we used gain-of-function Notch1 mice and demonstrated that Notch activation cell autonomously dictates luminal cell fate specification to both embryonic and basally committed mammary cells. These functional studies have important implications for understanding the signals underlying cell plasticity and serve to clarify how reactivation of embryonic programs in adult cells can lead to cancer.

Computational design of nanostructural color for additive manufacturing - Auzinger, Thomas; Heidrich, Wolfgang; Bickel, Bernd (ACM Transactions on Graphics)
Additive manufacturing has recently seen drastic improvements in resolution, making it now possible to fabricate features at scales of hundreds or even dozens of nanometers, which previously required very expensive lithographic methods. As a result, additive manufacturing now seems poised for optical applications, including those relevant to computer graphics, such as material design, as well as display and imaging applications. In this work, we explore the use of additive manufacturing for generating structural colors, where the structures are designed using a fabrication-aware optimization process. This requires a combination of full-wave simulation, a feasible parameterization of the design space, and a tailored optimization procedure. Many of these components should be re-usable for the design of other optical structures at this scale. We show initial results of material samples fabricated based on our designs. While these suffer from the prototype character of state-of-the-art fabrication hardware, we believe they clearly demonstrate the potential of additive nanofabrication for structural colors and other graphics applications.

CoreCavity: Interactive shell decomposition for fabrication with two-piece rigid molds - Nakashima, Kazutaka; Auzinger, Thomas; Iarussi, Emmanuel; Zhang, Ran; Igarashi, Takeo; Bickel, Bernd (ACM Transaction on Graphics)
Molding is a popular mass production method, in which the initial expenses for the mold are offset by the low per-unit production cost. However, the physical fabrication constraints of the molding technique commonly restrict the shape of moldable objects. For a complex shape, a decomposition of the object into moldable parts is a common strategy to address these constraints, with plastic model kits being a popular and illustrative example. However, conducting such a decomposition requires considerable expertise, and it depends on the technical aspects of the fabrication technique, as well as aesthetic considerations. We present an interactive technique to create such decompositions for two-piece molding, in which each part of the object is cast between two rigid mold pieces. Given the surface description of an object, we decompose its thin-shell equivalent into moldable parts by first performing a coarse decomposition and then utilizing an active contour model for the boundaries between individual parts. Formulated as an optimization problem, the movement of the contours is guided by an energy reflecting fabrication constraints to ensure the moldability of each part. Simultaneously, the user is provided with editing capabilities to enforce aesthetic guidelines. Our interactive interface provides control of the contour positions by allowing, for example, the alignment of part boundaries with object features. Our technique enables a novel workflow, as it empowers novice users to explore the design space, and it generates fabrication-ready two-piece molds that can be used either for casting or industrial injection molding of free-form objects.

Crosstalk in concurrent repeated games impedes direct reciprocity and requires stronger levels of forgiveness - Reiter, Johannes; Hilbe, Christian; Rand, David; Chatterjee, Krishnendu; Nowak, Martin (Nature Communications)
Direct reciprocity is a mechanism for cooperation among humans. Many of our daily interactions are repeated. We interact repeatedly with our family, friends, colleagues, members of the local and even global community. In the theory of repeated games, it is a tacit assumption that the various games that a person plays simultaneously have no effect on each other. Here we introduce a general framework that allows us to analyze “crosstalk” between a player’s concurrent games. In the presence of crosstalk, the action a person experiences in one game can alter the person’s decision in another. We find that crosstalk impedes the maintenance of cooperation and requires stronger levels of forgiveness. The magnitude of the effect depends on the population structure. In more densely connected social groups, crosstalk has a stronger effect. A harsh retaliator, such as Tit-for-Tat, is unable to counteract crosstalk. The crosstalk framework provides a unified interpretation of direct and upstream reciprocity in the context of repeated games.

Complementary tuning of Na+ and K+ channel gating underlies fast and energy-efficient action potentials in GABAergic interneuron axons - Hu, Hua; Roth, Fabian; Vandael, David H; Jonas, Peter M (Neuron)
Fast-spiking, parvalbumin-expressing GABAergic interneurons (PV+-BCs) express a complex machinery of rapid signaling mechanisms, including specialized voltage-gated ion channels to generate brief action potentials (APs). However, short APs are associated with overlapping Na+ and K+ fluxes and are therefore energetically expensive. How the potentially vicious combination of high AP frequency and inefficient spike generation can be reconciled with limited energy supply is presently unclear. To address this question, we performed direct recordings from the PV+-BC axon, the subcellular structure where active conductances for AP initiation and propagation are located. Surprisingly, the energy required for the AP was, on average, only ∼1.6 times the theoretical minimum. High energy efficiency emerged from the combination of fast inactivation of Na+ channels and delayed activation of Kv3-type K+ channels, which minimized ion flux overlap during APs. Thus, the complementary tuning of axonal Na+ and K+ channel gating optimizes both fast signaling properties and metabolic efficiency. Hu et al. demonstrate that action potentials in parvalbumin-expressing GABAergic interneuron axons are energetically efficient, which is highly unexpected given their brief duration. High energy efficiency emerges from the combination of fast inactivation of voltage-gated Na+ channels and delayed activation of Kv3 channels in the axon.

CRISPR-based herd immunity can limit phage epidemics in bacterial populations - Payne, Pavel; Geyrhofer, Lukas; Barton, Nicholas H; Bollback, Jonathan P (eLife)
Herd immunity, a process in which resistant individuals limit the spread of a pathogen among susceptible hosts has been extensively studied in eukaryotes. Even though bacteria have evolved multiple immune systems against their phage pathogens, herd immunity in bacteria remains unexplored. Here we experimentally demonstrate that herd immunity arises during phage epidemics in structured and unstructured Escherichia coli populations consisting of differing frequencies of susceptible and resistant cells harboring CRISPR immunity. In addition, we develop a mathematical model that quantifies how herd immunity is affected by spatial population structure, bacterial growth rate, and phage replication rate. Using our model we infer a general epidemiological rule describing the relative speed of an epidemic in partially resistant spatially structured populations. Our experimental and theoretical findings indicate that herd immunity may be important in bacterial communities, allowing for stable coexistence of bacteria and their phages and the maintenance of polymorphism in bacterial immunity.

Crossing minimization in perturbed drawings - Fulek, Radoslav; Tóth, Csaba D.
Due to data compression or low resolution, nearby vertices and edges of a graph drawing may be bundled to a common node or arc. We model such a “compromised” drawing by a piecewise linear map φ:G → ℝ. We wish to perturb φ by an arbitrarily small ε>0 into a proper drawing (in which the vertices are distinct points, any two edges intersect in finitely many points, and no three edges have a common interior point) that minimizes the number of crossings. An ε-perturbation, for every ε>0, is given by a piecewise linear map (Formula Presented), where with ||·|| is the uniform norm (i.e., sup norm). We present a polynomial-time solution for this optimization problem when G is a cycle and the map φ has no spurs (i.e., no two adjacent edges are mapped to overlapping arcs). We also show that the problem becomes NP-complete (i) when G is an arbitrary graph and φ has no spurs, and (ii) when φ may have spurs and G is a cycle or a union of disjoint paths.

Complexity of the laminar-turbulent boundary in pipe flow - Budanur, Nazmi B; Hof, Björn (Physical Review Fluids)
Over the past decade, the edge of chaos has proven to be a fruitful starting point for investigations of shear flows when the laminar base flow is linearly stable. Numerous computational studies of shear flows demonstrated the existence of states that separate laminar and turbulent regions of the state space. In addition, some studies determined invariant solutions that reside on this edge. In this paper, we study the unstable manifold of one such solution with the aid of continuous symmetry reduction, which we formulate here for the simultaneous quotiening of axial and azimuthal symmetries. Upon our investigation of the unstable manifold, we discover a previously unknown traveling-wave solution on the laminar-turbulent boundary with a relatively complex structure. By means of low-dimensional projections, we visualize different dynamical paths that connect these solutions to the turbulence. Our numerical experiments demonstrate that the laminar-turbulent boundary exhibits qualitatively different regions whose properties are influenced by the nearby invariant solutions.

Counting blanks in polygonal arrangements - Akopyan, Arseniy; Segal Halevi, Erel (SIAM Journal on Discrete Mathematics)
Inside a two-dimensional region (``cake""), there are m nonoverlapping tiles of a certain kind (``toppings""). We want to expand the toppings while keeping them nonoverlapping, and possibly add some blank pieces of the same ``certain kind,"" such that the entire cake is covered. How many blanks must we add? We study this question in several cases: (1) The cake and toppings are general polygons. (2) The cake and toppings are convex figures. (3) The cake and toppings are axis-parallel rectangles. (4) The cake is an axis-parallel rectilinear polygon and the toppings are axis-parallel rectangles. In all four cases, we provide tight bounds on the number of blanks.

Data from: CRISPR-based herd immunity limits phage epidemics in bacterial populations - Payne, Pavel; Geyrhofer, Lukas; Barton, Nicholas H; Bollback, Jonathan P
Herd immunity, a process in which resistant individuals limit the spread of a pathogen among susceptible hosts has been extensively studied in eukaryotes. Even though bacteria have evolved multiple immune systems against their phage pathogens, herd immunity in bacteria remains unexplored. Here we experimentally demonstrate that herd immunity arises during phage epidemics in structured and unstructured Escherichia coli populations consisting of differing frequencies of susceptible and resistant cells harboring CRISPR immunity. In addition, we develop a mathematical model that quantifies how herd immunity is affected by spatial population structure, bacterial growth rate, and phage replication rate. Using our model we infer a general epidemiological rule describing the relative speed of an epidemic in partially resistant spatially structured populations. Our experimental and theoretical findings indicate that herd immunity may be important in bacterial communities, allowing for stable coexistence of bacteria and their phages and the maintenance of polymorphism in bacterial immunity.

Destructive disinfection of infected brood prevents systemic disease spread in ant colonies - Pull, Christopher; Ugelvig, Line V; Wiesenhofer, Florian; Grasse, Anna V; Tragust, Simon; Schmitt, Thomas; Brown, Mark; Cremer, Sylvia (eLife)
Social insects protect their colonies from infectious disease through collective defences that result in social immunity. In ants, workers first try to prevent infection of colony members. Here, we show that if this fails and a pathogen establishes an infection, ants employ an efficient multicomponent behaviour − "destructive disinfection" − to prevent further spread of disease through the colony. Ants specifically target infected pupae during the pathogen's non-contagious incubation period, relying on chemical 'sickness cues' emitted by pupae. They then remove the pupal cocoon, perforate its cuticle and administer antimicrobial poison, which enters the body and prevents pathogen replication from the inside out. Like the immune system of a body that specifically targets and eliminates infected cells, this social immunity measure sacrifices infected brood to stop the pathogen completing its lifecycle, thus protecting the rest of the colony. Hence, the same principles of disease defence apply at different levels of biological organisation.

Defining lineage potential and fate behavior of precursors during pancreas development - Sznurkowska, Magdalena; Hannezo, Edouard B; Azzarelli, Roberta; Rulands, Steffen; Nestorowa, Sonia; Hindley, Christopher; Nichols, Jennifer; Göttgens, Berthold; Huch, Meritxell; Philpott, Anna; Simons, Benjamin (Developmental Cell)
Pancreas development involves a coordinated process in which an early phase of cell segregation is followed by a longer phase of lineage restriction, expansion, and tissue remodeling. By combining clonal tracing and whole-mount reconstruction with proliferation kinetics and single-cell transcriptional profiling, we define the functional basis of pancreas morphogenesis. We show that the large-scale organization of mouse pancreas can be traced to the activity of self-renewing precursors positioned at the termini of growing ducts, which act collectively to drive serial rounds of stochastic ductal bifurcation balanced by termination. During this phase of branching morphogenesis, multipotent precursors become progressively fate-restricted, giving rise to self-renewing acinar-committed precursors that are conveyed with growing ducts, as well as ductal progenitors that expand the trailing ducts and give rise to delaminating endocrine cells. These findings define quantitatively how the functional behavior and lineage progression of precursor pools determine the large-scale patterning of pancreatic sub-compartments.

Cup-shaped Cotyledon1 (CUC1) and CU2 regulate cytokinin homeostasis to determine ovule number in arabidopsis - Cucinotta, Mara; Manrique, Silvia; Cuesta, Candela; Benková, Eva; Novák, Ondřej; Colombo, Lucia (Journal of Experimental Botany)
Seeds derive from ovules upon fertilization and therefore the total number of ovules determines the final seed yield, a fundamental trait in crop plants. Among the factors that co-ordinate the process of ovule formation, the transcription factors CUP-SHAPED COTYLEDON 1 (CUC1) and CUC2 and the hormone cytokinin (CK) have a particularly prominent role. Indeed, the absence of both CUC1 and CUC2 causes a severe reduction in ovule number, a phenotype that can be rescued by CK treatment. In this study, we combined CK quantification with an integrative genome-wide target identification approach to select Arabidopsis genes regulated by CUCs that are also involved in CK metabolism. We focused our attention on the functional characterization of UDP-GLUCOSYL TRANSFERASE 85A3 (UGT85A3) and UGT73C1, which are up-regulated in the absence of CUC1 and CUC2 and encode enzymes able to catalyse CK inactivation by O-glucosylation. Our results demonstrate a role for these UGTs as a link between CUCs and CK homeostasis, and highlight the importance of CUCs and CKs in the determination of seed yield.

Design, synthesis and perception of fluorescently labeled isoprenoid cytokinins - Kubiasová, Karolina; Mik, Václav; Nisler, Jaroslav; Hönig, Martin; Husičková, Alexandra; Spíchal, Lukáš; Pěkná, Zuzana; Šamajová, Olga; Doležal, Karel; Plíhal, Ondřej; Benková, Eva; Strnad, Miroslav; et al. (Phytochemistry)
Isoprenoid cytokinins play a number of crucial roles in the regulation of plant growth and development. To study cytokinin receptor properties in plants, we designed and prepared fluorescent derivatives of 6-[(3-methylbut-2-en-1-yl)amino]purine (N6-isopentenyladenine, iP) with several fluorescent labels attached to the C2 or N9 atom of the purine moiety via a 2- or 6-carbon linker. The fluorescent labels included dansyl (DS), fluorescein (FC), 7-nitrobenzofurazan (NBD), rhodamine B (RhoB), coumarin (Cou), 7-(diethylamino)coumarin (DEAC) and cyanine 5 dye (Cy5). All prepared compounds were screened for affinity for the Arabidopsis thaliana cytokinin receptor (CRE1/AHK4). Although the attachment of the fluorescent labels to iP via the linkers mostly disrupted binding to the receptor, several fluorescent derivatives interacted well. For this reason, three derivatives, two rhodamine B and one 4-chloro-7-nitrobenzofurazan labeled iP were tested for their interaction with CRE1/AHK4 and Zea mays cytokinin receptors in detail. We further showed that the three derivatives were able to activate transcription of cytokinin response regulator ARR5 in Arabidopsis seedlings. The activity of fluorescently labeled cytokinins was compared with corresponding 6-dimethylaminopurine fluorescently labeled negative controls. Selected rhodamine B C2-labeled compounds 17, 18 and 4-chloro-7-nitrobenzofurazan N9-labeled compound 28 and their respective negative controls (19, 20 and 29, respectively) were used for in planta staining experiments in Arabidopsis thaliana cell suspension culture using live cell confocal microscopy.

Detection and characterization of many-body localization in central spin models - Hetterich, Daniel; Yao, Norman; Serbyn, Maksym; Pollmann, Frank; Trauzettel, Björn (Physical Review B)
We analyze a disordered central spin model, where a central spin interacts equally with each spin in a periodic one-dimensional (1D) random-field Heisenberg chain. If the Heisenberg chain is initially in the many-body localized (MBL) phase, we find that the coupling to the central spin suffices to delocalize the chain for a substantial range of coupling strengths. We calculate the phase diagram of the model and identify the phase boundary between the MBL and ergodic phase. Within the localized phase, the central spin significantly enhances the rate of the logarithmic entanglement growth and its saturation value. We attribute the increase in entanglement entropy to a nonextensive enhancement of magnetization fluctuations induced by the central spin. Finally, we demonstrate that correlation functions of the central spin can be utilized to distinguish between MBL and ergodic phases of the 1D chain. Hence, we propose the use of a central spin as a possible experimental probe to identify the MBL phase.

Drosophila TNF modulates tissue tension in the embryo to facilitate macrophage invasive migration - Ratheesh, Aparna; Biebl, Julia; Smutny, Michael; Veselá, Jana; Papusheva, Ekaterina; Krens, Gabriel; Kaufmann, Walter; György, Attila; Casano, Alessandra M; Siekhaus, Daria E (Developmental Cell)
Migrating cells penetrate tissue barriers during development, inflammatory responses, and tumor metastasis. We study if migration in vivo in such three-dimensionally confined environments requires changes in the mechanical properties of the surrounding cells using embryonic Drosophila melanogaster hemocytes, also called macrophages, as a model. We find that macrophage invasion into the germband through transient separation of the apposing ectoderm and mesoderm requires cell deformations and reductions in apical tension in the ectoderm. Interestingly, the genetic pathway governing these mechanical shifts acts downstream of the only known tumor necrosis factor superfamily member in Drosophila, Eiger, and its receptor, Grindelwald. Eiger-Grindelwald signaling reduces levels of active Myosin in the germband ectodermal cortex through the localization of a Crumbs complex component, Patj (Pals-1-associated tight junction protein). We therefore elucidate a distinct molecular pathway that controls tissue tension and demonstrate the importance of such regulation for invasive migration in vivo.

Drag enhancement and drag reduction in viscoelastic flow - Varshney, Atul; Steinberg, Victor (Physical Review Fluids)
Creeping flow of polymeric fluid without inertia exhibits elastic instabilities and elastic turbulence accompanied by drag enhancement due to elastic stress produced by flow-stretched polymers. However, in inertia-dominated flow at high Re and low fluid elasticity El, a reduction in turbulent frictional drag is caused by an intricate competition between inertial and elastic stresses. Here we explore the effect of inertia on the stability of viscoelastic flow in a broad range of control parameters El and (Re,Wi). We present the stability diagram of observed flow regimes in Wi-Re coordinates and find that the instabilities' onsets show an unexpectedly nonmonotonic dependence on El. Further, three distinct regions in the diagram are identified based on El. Strikingly, for high-elasticity fluids we discover a complete relaminarization of flow at Reynolds number in the range of 1 to 10, different from a well-known turbulent drag reduction. These counterintuitive effects may be explained by a finite polymer extensibility and a suppression of vorticity at high Wi. Our results call for further theoretical and numerical development to uncover the role of inertial effect on elastic turbulence in a viscoelastic flow.

Distributed and dynamic intracellular organization of extracellular information - Granados, Alejandro; Pietsch, Julian; Cepeda Humerez, Sarah A; Farquhar, Isebail; Tkacik, Gasper; Swain, Peter (PNAS)
Although cells respond specifically to environments, how environmental identity is encoded intracellularly is not understood. Here, we study this organization of information in budding yeast by estimating the mutual information between environmental transitions and the dynamics of nuclear translocation for 10 transcription factors. Our method of estimation is general, scalable, and based on decoding from single cells. The dynamics of the transcription factors are necessary to encode the highest amounts of extracellular information, and we show that information is transduced through two channels: Generalists (Msn2/4, Tod6 and Dot6, Maf1, and Sfp1) can encode the nature of multiple stresses, but only if stress is high; specialists (Hog1, Yap1, and Mig1/2) encode one particular stress, but do so more quickly and for a wider range of magnitudes. In particular, Dot6 encodes almost as much information as Msn2, the master regulator of the environmental stress response. Each transcription factor reports differently, and it is only their collective behavior that distinguishes between multiple environmental states. Changes in the dynamics of the localization of transcription factors thus constitute a precise, distributed internal representation of extracellular change. We predict that such multidimensional representations are common in cellular decision-making.

Distinct roles for plasma membrane PtdIns 4 P and PtdIns 4 5 P2 during yeast receptor mediated endocytosis - Yamamoto, Wataru; Wada, Suguru; Nagano, Makoto; Aoshima, Kaito; Siekhaus, Daria E; Toshima, Junko; Toshima, Jiro (Journal of Cell Science)
Clathrin-mediated endocytosis requires the coordinated assembly of various endocytic proteins and lipids at the plasma membrane. Accumulating evidence demonstrates a crucial role for phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2) in endocytosis, but specific roles for PtdIns(4)P other than as the biosynthetic precursor of PtdIns(4,5)P2 have not been clarified. In this study we investigated the role of PtdIns(4)P or PtdIns(4,5)P2 in receptor-mediated endocytosis through the construction of temperature-sensitive (ts) mutants for the PI 4-kinases Stt4p and Pik1p and the PtdIns(4) 5-kinase Mss4p. Quantitative analyses of endocytosis revealed that both the stt4(ts)pik1(ts) and mss4(ts) mutants have a severe defect in endocytic internalization. Live-cell imaging of endocytic protein dynamics in stt4(ts)pik1(ts) and mss4(ts) mutants revealed that PtdIns(4)P is required for the recruitment of the alpha-factor receptor Ste2p to clathrin-coated pits whereas PtdIns(4,5)P2 is required for membrane internalization. We also found that the localization to endocytic sites of the ENTH/ANTH domain-bearing clathrin adaptors, Ent1p/Ent2p and Yap1801p/Yap1802p, is significantly impaired in the stt4(ts)pik1(ts) mutant, but not in the mss4(ts) mutant. These results suggest distinct roles in successive steps for PtdIns(4)P and PtdIns(4,5)P2 during receptor-mediated endocytosis.

Efficient parametric identification for STL - Bakhirkin, Alexey; Ferrere, Thomas; Maler, Oded (Proceedings of the 21st International Conference on Hybrid Systems)
We describe a new algorithm for the parametric identification problem for signal temporal logic (STL), stated as follows. Given a densetime real-valued signal w and a parameterized temporal logic formula φ, compute the subset of the parameter space that renders the formula satisfied by the signal. Unlike previous solutions, which were based on search in the parameter space or quantifier elimination, our procedure works recursively on φ and computes the evolution over time of the set of valid parameter assignments. This procedure is similar to that of monitoring or computing the robustness of φ relative to w. Our implementation and experiments demonstrate that this approach can work well in practice.

Efficient algorithms for asymptotic bounds on termination time in VASS - Brázdil, Tomáš; Chatterjee, Krishnendu; Kučera, Antonín; Novotny, Petr; Velan, Dominik; Zuleger, Florian
Vector Addition Systems with States (VASS) provide a well-known and fundamental model for the analysis of concurrent processes, parameterized systems, and are also used as abstract models of programs in resource bound analysis. In this paper we study the problem of obtaining asymptotic bounds on the termination time of a given VASS. In particular, we focus on the practically important case of obtaining polynomial bounds on termination time. Our main contributions are as follows: First, we present a polynomial-time algorithm for deciding whether a given VASS has a linear asymptotic complexity. We also show that if the complexity of a VASS is not linear, it is at least quadratic. Second, we classify VASS according to quantitative properties of their cycles. We show that certain singularities in these properties are the key reason for non-polynomial asymptotic complexity of VASS. In absence of singularities, we show that the asymptotic complexity is always polynomial and of the form Θ(nk), for some integer k d, where d is the dimension of the VASS. We present a polynomial-time algorithm computing the optimal k. For general VASS, the same algorithm, which is based on a complete technique for the construction of ranking functions in VASS, produces a valid lower bound, i.e., a k such that the termination complexity is (nk). Our results are based on new insights into the geometry of VASS dynamics, which hold the potential for further applicability to VASS analysis.

Efficient optimization for rank-based loss functions - Mohapatra, Pritish; Rolinek, Michal; Jawahar, C V; Kolmogorov, Vladimir; Kumar, M Pawan (2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition)
The accuracy of information retrieval systems is often measured using complex loss functions such as the average precision (AP) or the normalized discounted cumulative gain (NDCG). Given a set of positive and negative samples, the parameters of a retrieval system can be estimated by minimizing these loss functions. However, the non-differentiability and non-decomposability of these loss functions does not allow for simple gradient based optimization algorithms. This issue is generally circumvented by either optimizing a structured hinge-loss upper bound to the loss function or by using asymptotic methods like the direct-loss minimization framework. Yet, the high computational complexity of loss-augmented inference, which is necessary for both the frameworks, prohibits its use in large training data sets. To alleviate this deficiency, we present a novel quicksort flavored algorithm for a large class of non-decomposable loss functions. We provide a complete characterization of the loss functions that are amenable to our algorithm, and show that it includes both AP and NDCG based loss functions. Furthermore, we prove that no comparison based algorithm can improve upon the computational complexity of our approach asymptotically. We demonstrate the effectiveness of our approach in the context of optimizing the structured hinge loss upper bound of AP and NDCG loss for learning models for a variety of vision tasks. We show that our approach provides significantly better results than simpler decomposable loss functions, while requiring a comparable training time.

Emergent dirac gullies and gully-symmetry-breaking quantum hall states in ABA trilayer graphene - Zibrov, Alexander; Peng, Rao; Kometter, Carlos; Li, Jia; Dean, Cory; Taniguchi, Takashi; Watanabe, Kenji; Serbyn, Maksym; Young, Andrea (Physical Review Letters)
We report on quantum capacitance measurements of high quality, graphite- and hexagonal boron nitride encapsulated Bernal stacked trilayer graphene devices. At zero applied magnetic field, we observe a number of electron density- and electrical displacement-tuned features in the electronic compressibility associated with changes in Fermi surface topology. At high displacement field and low density, strong trigonal warping gives rise to emergent Dirac gullies centered near the corners of the hexagonal Brillouin and related by three fold rotation symmetry. At low magnetic fields of B=1.25~T, the gullies manifest as a change in the degeneracy of the Landau levels from two to three. Weak incompressible states are also observed at integer filling within these triplets Landau levels, which a Hartree-Fock analysis indicates are associated with Coulomb-driven nematic phases that spontaneously break rotation symmetry.

Electromagnetic fields and optomechanics In cancer diagnostics and treatment - Salari, Vahid; Barzanjeh, Shabir; Cifra, Michal; Simon, Christoph; Scholkmann, Felix; Alirezaei, Zahra; Tuszynski, Jack (Frontiers in Bioscience - Landmark)
In this paper, we discuss biological effects of electromagnetic (EM) fields in the context of cancer biology. In particular, we review the nanomechanical properties of microtubules (MTs), the latter being one of the most successful targets for cancer therapy. We propose an investigation on the coupling of electromagnetic radiation to mechanical vibrations of MTs as an important basis for biological and medical applications. In our opinion, optomechanical methods can accurately monitor and control the mechanical properties of isolated MTs in a liquid environment. Consequently, studying nanomechanical properties of MTs may give useful information for future applications to diagnostic and therapeutic technologies involving non-invasive externally applied physical fields. For example, electromagnetic fields or high intensity ultrasound can be used therapeutically avoiding harmful side effects of chemotherapeutic agents or classical radiation therapy.

Embeddability in the 3-Sphere is decidable - Matoušek, Jiří; Sedgwick, Eric; Tancer, Martin; Wagner, Uli (Journal of the ACM)
We show that the following algorithmic problem is decidable: given a 2-dimensional simplicial complex, can it be embedded (topologically, or equivalently, piecewise linearly) in R3? By a known reduction, it suffices to decide the embeddability of a given triangulated 3-manifold X into the 3-sphere S3. The main step, which allows us to simplify X and recurse, is in proving that if X can be embedded in S3, then there is also an embedding in which X has a short meridian, that is, an essential curve in the boundary of X bounding a disk in S3 \ X with length bounded by a computable function of the number of tetrahedra of X.

Establishment in a new habitat by polygenic adaptation - Barton, Nicholas H; Etheridge, Alison (Theoretical Population Biology)
Maladapted individuals can only colonise a new habitat if they can evolve a positive growth rate fast enough to avoid extinction, a process known as evolutionary rescue. We treat log fitness at low density in the new habitat as a single polygenic trait and thus use the infinitesimal model to follow the evolution of the growth rate; this assumes that the trait values of offspring of a sexual union are normally distributed around the mean of the parents’ trait values, with variance that depends only on the parents’ relatedness. The probability that a single migrant can establish depends on just two parameters: the mean and genetic variance of the trait in the source population. The chance of success becomes small if migrants come from a population with mean growth rate in the new habitat more than a few standard deviations below zero; this chance depends roughly equally on the probability that the initial founder is unusually fit, and on the subsequent increase in growth rate of its offspring as a result of selection. The loss of genetic variation during the founding event is substantial, but highly variable. With continued migration at rate M, establishment is inevitable; when migration is rare, the expected time to establishment decreases inversely with M. However, above a threshold migration rate, the population may be trapped in a ‘sink’ state, in which adaptation is held back by gene flow; above this threshold, the expected time to establishment increases exponentially with M. This threshold behaviour is captured by a deterministic approximation, which assumes a Gaussian distribution of the trait in the founder population with mean and variance evolving deterministically. By assuming a constant genetic variance, we also develop a diffusion approximation for the joint distribution of population size and trait mean, which extends to include stabilising selection and density regulation. Divergence of the population from its ancestors causes partial reproductive isolation, which we measure through the reproductive value of migrants into the newly established population.

Evolution of cooperation in stochastic games - Hilbe, Christian; Šimsa, Štepán; Chatterjee, Krishnendu; Nowak, Martin (Nature)
Social dilemmas occur when incentives for individuals are misaligned with group interests 1-7 . According to the 'tragedy of the commons', these misalignments can lead to overexploitation and collapse of public resources. The resulting behaviours can be analysed with the tools of game theory 8 . The theory of direct reciprocity 9-15 suggests that repeated interactions can alleviate such dilemmas, but previous work has assumed that the public resource remains constant over time. Here we introduce the idea that the public resource is instead changeable and depends on the strategic choices of individuals. An intuitive scenario is that cooperation increases the public resource, whereas defection decreases it. Thus, cooperation allows the possibility of playing a more valuable game with higher payoffs, whereas defection leads to a less valuable game. We analyse this idea using the theory of stochastic games 16-19 and evolutionary game theory. We find that the dependence of the public resource on previous interactions can greatly enhance the propensity for cooperation. For these results, the interaction between reciprocity and payoff feedback is crucial: neither repeated interactions in a constant environment nor single interactions in a changing environment yield similar cooperation rates. Our framework shows which feedbacks between exploitation and environment - either naturally occurring or designed - help to overcome social dilemmas.

Evolutionary interplay between symbiotic relationships and patterns of signal peptide gain and loss - Hönigschmid, Peter; Bykova, Nadya; Schneider, René; Ivankov, Dmitry; Frishman, Dmitrij (Genome Biology and Evolution)
Can orthologous proteins differ in terms of their ability to be secreted? To answer this question, we investigated the distribution of signal peptides within the orthologous groups of Enterobacterales. Parsimony analysis and sequence comparisons revealed a large number of signal peptide gain and loss events, in which signal peptides emerge or disappear in the course of evolution. Signal peptide losses prevail over gains, an effect which is especially pronounced in the transition from the free-living or commensal to the endosymbiotic lifestyle. The disproportionate decline in the number of signal peptide-containing proteins in endosymbionts cannot be explained by the overall reduction of their genomes. Signal peptides can be gained and lost either by acquisition/elimination of the corresponding N-terminal regions or by gradual accumulation of mutations. The evolutionary dynamics of signal peptides in bacterial proteins represents a powerful mechanism of functional diversification.

Estimating barriers to gene flow from distorted isolation-by-distance patterns - Ringbauer, Harald; Kolesnikov, Alexander; Field, David; Barton, Nicholas H (Genetics)
In continuous populations with local migration, nearby pairs of individuals have on average more similar genotypes than geographically well separated pairs. A barrier to gene flow distorts this classical pattern of isolation by distance. Genetic similarity is decreased for sample pairs on different sides of the barrier and increased for pairs on the same side near the barrier. Here, we introduce an inference scheme that utilizes this signal to detect and estimate the strength of a linear barrier to gene flow in two-dimensions. We use a diffusion approximation to model the effects of a barrier on the geographical spread of ancestry backwards in time. This approach allows us to calculate the chance of recent coalescence and probability of identity by descent. We introduce an inference scheme that fits these theoretical results to the geographical covariance structure of bialleleic genetic markers. It can estimate the strength of the barrier as well as several demographic parameters. We investigate the power of our inference scheme to detect barriers by applying it to a wide range of simulated data. We also showcase an example application to a Antirrhinum majus (snapdragon) flower color hybrid zone, where we do not detect any signal of a strong genome wide barrier to gene flow.

Extended narrow band FLIP for liquid simulations - Sato, Takahiro; Wojtan, Christopher J; Thuerey, Nils; Igarashi, Takeo; Ando, Ryoichi (Computer Graphics Forum)
The Fluid Implicit Particle method (FLIP) reduces numerical dissipation by combining particles with grids. To improve performance, the subsequent narrow band FLIP method (NB‐FLIP) uses a FLIP‐based fluid simulation only near the liquid surface and a traditional grid‐based fluid simulation away from the surface. This spatially‐limited FLIP simulation significantly reduces the number of particles and alleviates a computational bottleneck. In this paper, we extend the NB‐FLIP idea even further, by allowing a simulation to transition between a FLIP‐like fluid simulation and a grid‐based simulation in arbitrary locations, not just near the surface. This approach leads to even more savings in memory and computation, because we can concentrate the particles only in areas where they are needed. More importantly, this new method allows us to seamlessly transition to smooth implicit surface geometry wherever the particle‐based simulation is unnecessary. Consequently, our method leads to a practical algorithm for avoiding the noisy surface artifacts associated with particle‐based liquid simulations, while simultaneously maintaining the benefits of a FLIP simulation in regions of dynamic motion.

Evolutionary pathways for the generation of new self-incompatibility haplotypes in a non-self recognition system - Bodova, Katarina; Priklopil, Tadeas; Field, David; Barton, Nicholas H; Pickup, Melinda (Genetics)
Self-incompatibility (SI) is a genetically based recognition system that functions to prevent self-fertilization and mating among related plants. An enduring puzzle in SI is how the high diversity observed in nature arises and is maintained. Based on the underlying recognition mechanism, SI can be classified into two main groups: self- and non-self recognition. Most work has focused on diversification within self-recognition systems despite expected differences between the two groups in the evolutionary pathways and outcomes of diversification. Here, we use a deterministic population genetic model and stochastic simulations to investigate how novel S-haplotypes evolve in a gametophytic non-self recognition (SRNase/S Locus F-box (SLF)) SI system. For this model the pathways for diversification involve either the maintenance or breakdown of SI and can vary in the order of mutations of the female (SRNase) and male (SLF) components. We show analytically that diversification can occur with high inbreeding depression and self-pollination, but this varies with evolutionary pathway and level of completeness (which determines the number of potential mating partners in the population), and in general is more likely for lower haplotype number. The conditions for diversification are broader in stochastic simulations of finite population size. However, the number of haplotypes observed under high inbreeding and moderate to high self-pollination is less than that commonly observed in nature. Diversification was observed through pathways that maintain SI as well as through self-compatible intermediates. Yet the lifespan of diversified haplotypes was sensitive to their level of completeness. By examining diversification in a non-self recognition SI system, this model extends our understanding of the evolution and maintenance of haplotype diversity observed in a self recognition system common in flowering plants.

Expansions of key protein families in the German cockroach highlight the molecular basis of its remarkable success as a global indoor pest - Harrison, Mark; Arning, Nicolas; Kremer, Lucas; Ylla, Guillem; Belles, Xavier; Bornberg Bauer, Erich; Huylmans, Ann K; Jongepier, Evelien; Puilachs, Maria; Richards, Stephen; Schal, Coby (Journal of Experimental Zoology Part B: Molecular and Developmental Evolution)
The German cockroach, Blattella germanica, is a worldwide pest that infests buildings, including homes, restaurants, and hospitals, often living in unsanitary conditions. As a disease vector and producer of allergens, this species has major health and economic impacts on humans. Factors contributing to the success of the German cockroach include its resistance to a broad range of insecticides, immunity to many pathogens, and its ability, as an extreme generalist omnivore, to survive on most food sources. The recently published genome shows that B. germanica has an exceptionally high number of protein coding genes. In this study, we investigate the functions of the 93 significantly expanded gene families with the aim to better understand the success of B. germanica as a major pest despite such inhospitable conditions. We find major expansions in gene families with functions related to the detoxification of insecticides and allelochemicals, defense against pathogens, digestion, sensory perception, and gene regulation. These expansions might have allowed B. germanica to develop multiple resistance mechanisms to insecticides and pathogens, and enabled a broad, flexible diet, thus explaining its success in unsanitary conditions and under recurrent chemical control. The findings and resources presented here provide insights for better understanding molecular mechanisms that will facilitate more effective cockroach control.

Existence of positive solutions to stochastic thin-film equations - Fischer, Julian L; Grün, Günther (SIAM Journal on Mathematical Analysis)
We construct martingale solutions to stochastic thin-film equations by introducing a (spatial) semidiscretization and establishing convergence. The discrete scheme allows for variants of the energy and entropy estimates in the continuous setting as long as the discrete energy does not exceed certain threshold values depending on the spatial grid size $h$. Using a stopping time argument to prolongate high-energy paths constant in time, arbitrary moments of coupled energy/entropy functionals can be controlled. Having established Hölder regularity of approximate solutions, the convergence proof is then based on compactness arguments---in particular on Jakubowski's generalization of Skorokhod's theorem---weak convergence methods, and recent tools on martingale convergence.

Supplemental material for Bodova et al., 2018 - Bod'ová, Katarína; Priklopil, Tadeas; Field, David; Barton, Nicholas H; Pickup, Melinda
File S1 contains figures that clarify the following features: (i) effect of population size on the average number/frequency of SI classes, (ii) changes in the minimal completeness deficit in time for a single class, and (iii) diversification diagrams for all studied pathways, including the summary figure for k = 8. File S2 contains the code required for a stochastic simulation of the SLF system with an example. This file also includes the output in the form of figures and tables.

Genetically encodable bioluminescent system from fungi - Kotlobay, Alexey A.; Sarkisyan, Karen; Mokrushina, Yuliana A.; Marcet-Houben, Marina; Serebrovskaya, Ekaterina O.; Markina, Nadezhda M.; Gonzalez Somermeyer, Louisa; Gorokhovatsky, Andrey Y.; Vvedensky, Andrey; Purtov, Konstantin V.; Petushkov, Valentin N.; Rodionova, Natalja S.; et al. (Proceedings of the National Academy of Sciences of the United States of America)
Bioluminescence is found across the entire tree of life, conferring a spectacular set of visually oriented functions from attracting mates to scaring off predators. Half a dozen different luciferins, molecules that emit light when enzymatically oxidized, are known. However, just one biochemical pathway for luciferin biosynthesis has been described in full, which is found only in bacteria. Here, we report identification of the fungal luciferase and three other key enzymes that together form the biosynthetic cycle of the fungal luciferin from caffeic acid, a simple and widespread metabolite. Introduction of the identified genes into the genome of the yeast Pichia pastoris along with caffeic acid biosynthesis genes resulted in a strain that is autoluminescent in standard media. We analyzed evolution of the enzymes of the luciferin biosynthesis cycle and found that fungal bioluminescence emerged through a series of events that included two independent gene duplications. The retention of the duplicated enzymes of the luciferin pathway in nonluminescent fungi shows that the gene duplication was followed by functional sequence divergence of enzymes of at least one gene in the biosynthetic pathway and suggests that the evolution of fungal bioluminescence proceeded through several closely related stepping stone nonluminescent biochemical reactions with adaptive roles. The availability of a complete eukaryotic luciferin biosynthesis pathway provides several applications in biomedicine and bioengineering.

Gibberellin DELLA signaling targets the retromer complex to redirect protein trafficking to the plasma membrane - Salanenka, Yuliya; Verstraeten, Inge; Löfke, Christian; Tabata, Kaori; Naramoto, Satoshi; Glanc, Matous; Friml, Jirí (PNAS)
The plant hormone gibberellic acid (GA) is a crucial regulator of growth and development. The main paradigm of GA signaling puts forward transcriptional regulation via the degradation of DELLA transcriptional repressors. GA has also been shown to regulate tropic responses by modulation of the plasma membrane incidence of PIN auxin transporters by an unclear mechanism. Here we uncovered the cellular and molecular mechanisms by which GA redirects protein trafficking and thus regulates cell surface functionality. Photoconvertible reporters revealed that GA balances the protein traffic between the vacuole degradation route and recycling back to the cell surface. Low GA levels promote vacuolar delivery and degradation of multiple cargos, including PIN proteins, whereas high GA levels promote their recycling to the plasma membrane. This GA effect requires components of the retromer complex, such as Sorting Nexin 1 (SNX1) and its interacting, microtubule (MT)-associated protein, the Cytoplasmic Linker-Associated Protein (CLASP1). Accordingly, GA regulates the subcellular distribution of SNX1 and CLASP1, and the intact MT cytoskeleton is essential for the GA effect on trafficking. This GA cellular action occurs through DELLA proteins that regulate the MT and retromer presumably via their interaction partners Prefoldins (PFDs). Our study identified a branching of the GA signaling pathway at the level of DELLA proteins, which, in parallel to regulating transcription, also target by a nontranscriptional mechanism the retromer complex acting at the intersection of the degradation and recycling trafficking routes. By this mechanism, GA can redirect receptors and transporters to the cell surface, thus coregulating multiple processes, including PIN-dependent auxin fluxes during tropic responses.

Flexible learning-free segmentation and reconstruction of neural volumes - Shabazi, Ali; Kinnison, Jeffery; Vescovi, Rafael; Du, Ming; Hill, Robert; Jösch, Maximilian A; Takeno, Marc; Zeng, Hongkui; Da Costa, Nuno; Grutzendler, Jaime; Kasthuri, Narayanan; Scheirer, Walter (Scientific Reports)
Imaging is a dominant strategy for data collection in neuroscience, yielding stacks of images that often scale to gigabytes of data for a single experiment. Machine learning algorithms from computer vision can serve as a pair of virtual eyes that tirelessly processes these images, automatically detecting and identifying microstructures. Unlike learning methods, our Flexible Learning-free Reconstruction of Imaged Neural volumes (FLoRIN) pipeline exploits structure-specific contextual clues and requires no training. This approach generalizes across different modalities, including serially-sectioned scanning electron microscopy (sSEM) of genetically labeled and contrast enhanced processes, spectral confocal reflectance (SCoRe) microscopy, and high-energy synchrotron X-ray microtomography (μCT) of large tissue volumes. We deploy the FLoRIN pipeline on newly published and novel mouse datasets, demonstrating the high biological fidelity of the pipeline’s reconstructions. FLoRIN reconstructions are of sufficient quality for preliminary biological study, for example examining the distribution and morphology of cells or extracting single axons from functional data. Compared to existing supervised learning methods, FLoRIN is one to two orders of magnitude faster and produces high-quality reconstructions that are tolerant to noise and artifacts, as is shown qualitatively and quantitatively.

Fast and efficient genetic engineering of hematopoietic precursor cells for the study of dendritic cell migration - Leithner, Alexander F; Renkawitz, Jörg; De Vries, Ingrid; Hauschild, Robert; Haecker, Hans; Sixt, Michael K (European Journal of Immunology)
Dendritic cells (DCs) are sentinels of the adaptive immune system that reside in peripheral organs of mammals. Upon pathogen encounter, they undergo maturation and up-regulate the chemokine receptor CCR7 that guides them along gradients of its chemokine ligands CCL19 and 21 to the next draining lymph node. There, DCs present peripherally acquired antigen to naïve T cells, thereby triggering adaptive immunity.

Genotype and diet affect resistance, survival, and fecundity but not fecundity tolerance - Kutzer, Megan; Kurtz, Joachim; Armitage, Sophie (Journal of Evolutionary Biology)
Insects are exposed to a variety of potential pathogens in their environment, many of which can severely impact fitness and health. Consequently, hosts have evolved resistance and tolerance strategies to suppress or cope with infections. Hosts utilizing resistance improve fitness by clearing or reducing pathogen loads, and hosts utilizing tolerance reduce harmful fitness effects per pathogen load. To understand variation in, and selective pressures on, resistance and tolerance, we asked to what degree they are shaped by host genetic background, whether plasticity in these responses depends upon dietary environment, and whether there are interactions between these two factors. Females from ten wild-type Drosophila melanogaster genotypes were kept on high- or low-protein (yeast) diets and infected with one of two opportunistic bacterial pathogens, Lactococcus lactis or Pseudomonas entomophila. We measured host resistance as the inverse of bacterial load in the early infection phase. The relationship (slope) between fly fecundity and individual-level bacteria load provided our fecundity tolerance measure. Genotype and dietary yeast determined host fecundity and strongly affected survival after infection with pathogenic P. entomophila. There was considerable genetic variation in host resistance, a commonly found phenomenon resulting from for example varying resistance costs or frequency-dependent selection. Despite this variation and the reproductive cost of higher P. entomophila loads, fecundity tolerance did not vary across genotypes. The absence of genetic variation in tolerance may suggest that at this early infection stage, fecundity tolerance is fixed or that any evolved tolerance mechanisms are not expressed under these infection conditions.

Genomics in neurodevelopmental disorders: an avenue to personalized medicine - Tarlungeanu, Dora-Clara; Novarino, Gaia (Experimental & Molecular Medicine)
Despite the remarkable number of scientific breakthroughs of the last 100 years, the treatment of neurodevelopmental disorders (e.g., autism spectrum disorder, intellectual disability) remains a great challenge. Recent advancements in genomics, such as whole-exome or whole-genome sequencing, have enabled scientists to identify numerous mutations underlying neurodevelopmental disorders. Given the few hundred risk genes that have been discovered, the etiological variability and the heterogeneous clinical presentation, the need for genotype — along with phenotype- based diagnosis of individual patients has become a requisite. In this review we look at recent advancements in genomic analysis and their translation into clinical practice.

Fermionic behavior of ideal anyons - Lundholm, Douglas; Seiringer, Robert (Letters in Mathematical Physics)
We prove upper and lower bounds on the ground-state energy of the ideal two-dimensional anyon gas. Our bounds are extensive in the particle number, as for fermions, and linear in the statistics parameter (Formula presented.). The lower bounds extend to Lieb–Thirring inequalities for all anyons except bosons.